Laminated film and molded article, and methods for producing the same

By using a photocurable layer with an average roughness RA of less than 0.05 μm and a transparent support substrate on the photo-drying layer, combined with a hard coat layer, the problem of surface unevenness of the photo-drying layer is solved, and a photo-drying layer with high wear resistance and good visibility is achieved, which is suitable for three-dimensional molding.

JP7624337B2Active Publication Date: 2025-01-30NIPPON PAINT AUTOMOTIVE COATINGS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021054543
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-01-30
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

In the prior art, the surface of the light-drying cover made of hollow resin particles is prone to unevenness, resulting in problems such as increasing haze, whitening appearance and reduced wear resistance.

Method used

A photo-curable layer with an average roughness RA of 0.05 μm is used, and a photo-curable layer formation method containing hollow resin particles is used. Combined with a transparent support substrate, a curable hard coating and a photo-curable coating layer, the interlayer adhesion and smooth surface are ensured by controlling the irradiation of light amount and energy lines.

Benefits of technology

High wear resistance and good visibility of the photo-drying layer are achieved, haze is reduced, appearance quality is maintained for a long time, and cracks and deformation are avoided during the three-dimensional forming process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624337000005
    Figure 0007624337000005
  • Figure 0007624337000006
    Figure 0007624337000006
  • Figure 0007624337000007
    Figure 0007624337000007
Patent Text Reader

Abstract

To provide an after-cure type laminated film which is excellent in abrasion resistance and a molded body, and a method for manufacturing them.SOLUTION: A laminated film includes a transparent support base material, an uncured hard coat layer formed on at least one surface of the transparent support base material, and an uncured light interference layer formed on the uncured hard coat layer. The uncured light interference layer contains hollow resin particles, and the arithmetic average roughness Ra of the surface of the uncured light interference layer is 0.05 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated film and a molded article, as well as methods for producing the same. [Background technology]

[0002] Displays are used in a variety of fields, including computers, televisions, mobile phones, and portable information terminal devices (tablet PCs, mobile devices, electronic organizers, etc.), as well as in digital meters, instrument panels, navigation systems, console panels, center clusters, heater control panels, and other in-vehicle display panels. Such products are often covered with a protective material. The protective material is usually obtained by forming a film having a hard coat layer.

[0003] In some cases, a low refractive index layer is further provided on the protective material for a display in order to reduce the reflectance of the surface on the viewing side. Patent Document 1 teaches a laminated film in which a hard coat layer and a low refractive index layer (light interference layer) are laminated in this order on a transparent support. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-004937 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the light interference layer, porous or hollow silica particles are usually blended as low refractive index particles. In recent years, it has been proposed to use hollow resin particles instead of hollow silica particles. This is because hollow resin particles have alkali resistance and excellent affinity with resin compositions. However, when hollow resin particles are used, unevenness may be formed on the surface of the obtained laminate film on the light interference layer side. The unevenness of the surface increases the haze of the laminate film, making the appearance whitish, and is likely to reduce abrasion resistance.

[0006] The present invention is intended to solve the above-mentioned problems in the prior art, and an object of the present invention is to provide an after-cure type laminate film and molded article having excellent abrasion resistance, as well as methods for producing the same. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention provides the following aspects. [1] A transparent support substrate; an uncured hard coat layer formed on at least one surface of the transparent support substrate; and an uncured optical interference layer formed on the uncured hard coat layer, the uncured light interference layer contains hollow resin particles, The uncured light interference layer has a surface with an arithmetic mean roughness Ra of 0.05 μm or less.

[0008] [2] Accumulated light intensity: 2000mJ / cm 2 The surface of the optical interference layer irradiated with the active energy ray was subjected to a pressure of 19.6 N / 4 cm 2 The laminate film according to the above-mentioned [1], wherein after being abraded 10,000 times at 1000° C., no scratches are visible on the optical interference layer.

[0009] [3] The laminate film according to the above-mentioned [1] or [2], wherein the average particle diameter of the hollow resin particles is 40% or more and 125% or less of the thickness of the uncured light interference layer.

[0010] [4] the uncured light interference layer contains an active energy ray-curable light interference layer-forming composition, The laminate film according to any one of the above [1] to [3], wherein the content of the hollow resin particles is 15 parts by mass or more and 80 parts by mass or less with respect to 100 parts by mass of the solid content of the optical interference layer-forming composition.

[0011] [5] the uncured light interference layer contains an active energy ray-curable light interference layer-forming composition, The optical interference layer-forming composition includes a first layer-forming component, the first layer-forming component includes a first reactive component having two or more polymerizable functional groups in one molecule; The laminate film according to any one of the above [1] to [4], wherein the first reactive component includes at least one of a first oligomer having a weight average molecular weight of 10,000 or less and a first monomer having a weight average molecular weight of 10,000 or less.

[0012] [6] The laminate film according to [5] above, wherein the total content of the first oligomer and the first monomer is 5 parts by mass or more and 55 parts by mass or less per 100 parts by mass of the solid content of the optical interference layer-forming composition.

[0013] [7] Accumulated light intensity: 2000mJ / cm 2 The laminate film according to any one of the above [1] to [6], wherein after the laminate film irradiated with the active energy rays is immersed in a 0.001 N aqueous sodium hydroxide solution and heated at a temperature of 55°C for 4 hours, no abnormality in appearance is visually observed on the surface of the optical interference layer.

[0014] [8] The laminated film according to any one of the above [1] to [7], wherein the stretch ratio of the laminated film at 160° C. is 50% or more.

[0015] [9] The laminate film according to any one of the above [1] to [8], wherein the luminous reflectance including specular reflected light in a wavelength range of 380 nm or more and 780 nm or less, measured from the uncured optical interference layer side, is 0.1% or more and 4.0% or less.

[0016]

[10] The laminate film according to any one of the above [1] to [9], wherein the uncured optical interference layer has a thickness of 15 nm or more and 200 nm or less.

[0017]

[11] The laminate film according to any one of the above [1] to

[10] , wherein the transparent supporting substrate has a thickness of 50 μm or more and 600 μm or less.

[0018]

[12] The laminate film according to any one of the above [1] to

[11] , wherein the uncured hard coat layer has a thickness of 2 μm or more and 30 μm or less.

[0019]

[13] The laminate film according to any one of the above [1] to

[12] , further comprising at least one uncured functional layer between the uncured hard coat layer and the uncured light interference layer.

[0020]

[14] The hardness H measured by the nanoindentation method from the uncured optical interference layer side BC The laminated film according to any one of the above [1] to

[13] , wherein the compressive strength is 0.05 GPa or more and 0.5 GPa or less.

[0021]

[15] Accumulated light intensity: 2000mJ / cm 2 The hardness H measured by a nanoindentation method from the light interference layer side of the laminated film irradiated with active energy rays of AC The laminated film according to any one of the above [1] to

[14] , wherein the compressive strength is 0.25 GPa or more and 0.7 GPa or less.

[0022]

[16] The uncured hard coat layer contains an active energy ray-curable hard coat layer-forming composition, The hard coat layer-forming composition includes a second layer-forming component, the second layer-forming component includes a second reactive component having two or more polymerizable functional groups in one molecule, The laminate film according to any one of the above [1] to

[15] , wherein the second reactive component includes at least one of a second oligomer having a weight average molecular weight of 10,000 or less and a second monomer having a weight average molecular weight of 10,000 or less.

[0023]

[17] The laminated film according to

[16] above, wherein the second reactive component further comprises a second polymer having a weight average molecular weight of more than 10,000.

[0024]

[18] The laminate film according to

[16] or

[17] above, wherein a total content of the second oligomer and the second monomer is 25 parts by mass or more and 65 parts by mass or less per 100 parts by mass of a solid content of the hard coat layer-forming composition.

[0025]

[19] A molded article comprising the cured laminate film according to any one of the above [1] to

[18] .

[0026]

[20] A step of forming an uncured hard coat layer on one surface of a transparent support substrate; forming an uncured optical interference layer on one surface of another supporting substrate; a lamination step of bonding a surface of the uncured hard coat layer opposite to the transparent support substrate and a surface of the uncured light interference layer opposite to the other support substrate to obtain a laminated film, the uncured light interference layer contains hollow resin particles, The method for producing a laminated film, wherein the uncured light interference layer of the resulting laminated film has an arithmetic mean roughness Ra of 0.05 μm or less.

[0027] [twenty one] A decorating step of forming a decorative layer on the other main surface of the transparent support substrate of the laminate film according to any one of the above [1] to

[18] ; The method for producing a molded body includes, after the decorating step, a curing step of irradiating the laminate film with active energy rays.

[0028] [twenty two] The method for producing a molded product according to the above-mentioned

[21] , further comprising, after the decorating step, an injection molding step of opposing the optical interference layer to a mold and injecting a molding resin toward the decorative layer.

[0029] [twenty three] The mold imparts a three-dimensional shape to the laminate film, The method for producing a molded article according to the above-mentioned

[22] , further comprising a preforming step of molding the laminate film into a shape that conforms to the three-dimensional shape after the decorating step and before the injection molding step. Effect of the Invention

[0030] According to the present invention, it is possible to provide an after-cure type laminate film and molded article having excellent abrasion resistance, as well as a method for producing the same. [Brief description of the drawings]

[0031] [Figure 1] 1 is a cross-sectional view illustrating a laminated film according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view that illustrates a molded article according to one embodiment of the present invention. [Diagram 3] 1 is a flowchart showing a method for producing a laminated film according to one embodiment of the present invention. [Figure 4] FIG. 2 is a schematic diagram illustrating a lamination step in a method for producing a laminated film according to one embodiment of the present invention. [Diagram 5] 1 is a flowchart showing a method for producing a molded body according to one embodiment of the present invention. [Figure 6] 10 is a flowchart showing a method for producing a molded body according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] Conventionally, a laminated film called a pre-cure type has been used as a protective film for a display. As shown in Patent Document 1, in the pre-cure type laminated film, the hard coat layer and the optical interference layer are cured.

[0033] When hollow resin particles are used in a pre-cured laminate film, the reason why unevenness is formed on the surface of the light interference layer is thought to be due to the behavior of the hollow resin particles in the process of forming the light interference layer. The light interference layer of a pre-cured laminate film is usually formed by coating a resin composition containing hollow resin particles on a cured hard coat layer, and then drying and curing. When the resin composition is heated to dry it, the thermal motion of the hollow resin particles themselves becomes active, and the fluidity of resin components having similar specific gravity increases, so that the hollow resin particles are placed in a situation where they are likely to move in the uncured light interference layer. Then, in the process in which the volatile components (typically, solvents) contained in the resin composition volatilize from the surface of the light interference layer and the light interference layer becomes thinner, the hollow resin particles that have moved together with the resin components are more likely to be present in the vicinity of the outer surface of the light interference layer. Therefore, the hollow resin particles are easily exposed from the surface of the light interference layer. As a result, unevenness originating from the hollow resin particles is likely to be formed on the surface of the light interference layer formed by a coating method on the hard coat layer. When hollow silica particles are used as the low refractive index particles, unevenness is unlikely to be formed on the surface of the light interference layer, probably because the hollow silica particles have a sufficiently larger specific gravity than the resin component. However, the hollow silica particles have poor affinity with the resin composition and therefore tend to fall off, which reduces the abrasion resistance.

[0034] This embodiment proposes a laminated film having a light interference layer having a smooth surface while containing hollow resin particles. Specifically, the arithmetic mean roughness Ra of the uncured light interference layer surface is 0.05 μm or less. As a result, the laminated film according to this embodiment exhibits excellent abrasion resistance and maintains good visibility for a long period of time. Furthermore, the haze caused by the unevenness of the surface is suppressed, resulting in a good appearance.

[0035] A. Laminated film The laminated film according to the present embodiment has a transparent supporting substrate, an uncured hard coat layer formed on at least one surface of the transparent supporting substrate, and an uncured light interference layer formed on the uncured hard coat layer. A laminated film having an uncured hard coat layer and an uncured light interference layer, which is cured after being formed into a three-dimensional shape, is called an after-cure type.

[0036] When using an after-cure type laminate film, the laminate film is in an uncured state, so that the occurrence of cracks and whitening during the molding process into a three-dimensional shape (typically, preforming or injection molding) is suppressed. Therefore, the appearance of the molded product is good. Furthermore, since cracks are unlikely to occur, the functions of the hard coat layer and the light interference layer are more effectively exerted.

[0037] The functions of the hard coat layer and the light interference layer are, for example, excellent hard coat performance and anti-reflection performance. The hard coat performance includes, for example, high hardness, abrasion resistance, and chemical resistance.

[0038] In particular, the laminated film is stretched during preforming. When an after-cure type laminated film is used, the stretching process is performed on the uncured laminated film, and excessive stretching process is not performed after curing. Therefore, each layer can be formed from a layer-forming composition that has a high crosslink density. In other words, the hardness of each layer after curing can be increased, and sufficient mechanical properties and chemical resistance can be easily obtained.

[0039] The term "uncured" refers to a state in which the film is not completely cured. The hard coat layer and the optical interference layer included in the laminate film may be in a semi-cured state.

[0040] Curing (complete curing) is synonymous with "cured and dried" as defined in JIS K 5500 (paint terminology). That is, curing refers to the state in which a) the coating surface is dry and hard, when the center of a test piece is pinched firmly between the thumb and index finger, no indentation is left on the coating surface due to fingerprints, no movement of the coating film is felt, and when the coating surface is rubbed rapidly and repeatedly with the fingertips, no scratches are left.

[0041] Accumulated light intensity: 200mJ / cm 2 It can be said that the laminated film irradiated with the above-mentioned active energy rays is completely cured.

[0042] Semi-curing is synonymous with "semi-cured dry" as defined in JIS K 5500 (paint terminology). In other words, semi-curing refers to the state when the painted surface is dry to the touch and no scratches are left when the center of the painted surface is rubbed lightly with a fingertip. 2 More than 200mJ / cm 2 A laminated film irradiated with active energy rays of less than 1000 nm can be said to be semi-cured.

[0043] The hard coat layer and the optical interference layer are not exposed to active energy rays or are exposed to less than 1 mJ / cm 2 When exposed to actinic energy rays for less than 100 sec, the film is considered to be uncured.

[0044] (Arithmetic surface roughness) The uncured optical interference layer has a surface with an arithmetic mean roughness Ra of 0.05 μm or less. This improves the abrasion resistance of the cured laminate film. The arithmetic mean roughness Ra is preferably 0.04 μm or less, and more preferably 0.03 μm or less.

[0045] Arithmetic surface roughness Ra is a type of parameter that indicates the unevenness (roughness profile) of a surface, as specified in Annex JA of JIS B0601;2001. Arithmetic surface roughness Ra is the average value of the absolute value of Z(x) in the reference length of the roughness curve. The roughness curve is obtained by applying a cutoff value phase compensation bandpass filter to the measured profile curve. Arithmetic surface roughness Ra is measured, for example, using a laser microscope.

[0046] The arithmetic mean roughness Ra is preferably measured for the laminate film immediately before curing. In the curing process, the smoothness of the surface of the optical interference layer does not change much. Therefore, the abrasion resistance of the molded body is affected by the smoothness of the surface of the optical interference layer immediately before curing. The arithmetic mean roughness Ra may be measured after the laminate film is heat-treated and / or after the preforming process described below and before curing. For example, the arithmetic mean roughness Ra of the laminate film that has been heat-treated for 30 to 60 seconds in an atmosphere of 150°C to 190°C may be 0.05 μm or less.

[0047] When the arithmetic mean roughness of the optical interference layer of the cured laminate film (ie, molded product) is 0.05 μm or less, the arithmetic mean roughness Ra of the laminate film immediately before curing can also be considered to be 0.05 μm or less.

[0048] The luminous reflectance and hardness before curing described later may also be measured using the laminate film immediately before curing after heat treatment under the above conditions. The static friction coefficient, abrasion resistance, alkali resistance, and hardness after curing may also be measured using the laminate film cured after heat treatment under the above conditions.

[0049] (Wear resistance) The laminated film according to this embodiment can provide a molded article with excellent abrasion resistance. 2 The surface of the optical interference layer of the laminated film irradiated with active energy rays of 4 cm 2The light interference layer was abraded 10,000 times while applying a normal load of 19.6 N per unit area. After this abrasion test, no scratches were visible on the light interference layer. The absence of visible scratches means that the deterioration of visibility due to changes in appearance is suppressed.

[0050] "No visible scratches" means that scratches cannot be observed by visual inspection. "Scratches" refer to, for example, surface roughness. As long as scratches are not observed by visual inspection, very slight scratches may be observed when observing the sample after the abrasion test using a microscope with a magnification of 100 times.

[0051] The abrasion test is carried out under the above conditions using a known method. Abrasion tests are usually carried out using a frictional device with a cotton cloth fixed to it. The frictional device is used to apply a 4 cm 2 A vertical load of 19.6N can be applied per unit area.

[0052] The laminated film has excellent abrasion resistance and a small static friction coefficient. Accumulated light intensity: 2000 mJ / cm 2 The static friction coefficient μ of the light interference layer of the laminated film irradiated with the active energy rays AC is, for example, 0.35 or less. The static friction coefficient is measured in accordance with JIS K 7125. The static friction coefficient μ AC may be less than or equal to 0.3, less than or equal to 0.25, and less than or equal to 0.20.

[0053] (Alkaline resistance) It is desirable for the laminated film to have excellent alkali resistance. For example, 2 The laminated film irradiated with the active energy rays is immersed in a 0.001N aqueous sodium hydroxide solution and heat-treated at a temperature of 55°C for 4 hours. It is preferable that no abnormality in appearance is visually observed on the surface of the light interference layer after this immersion test. The fact that no abnormality in appearance is visually observed means that a decrease in visibility due to a change in appearance is suppressed. A laminated film that does not contain hollow silica particles or in which the use of hollow silica particles is suppressed is likely to have improved alkali resistance.

[0054] "No visible abnormalities in appearance" means that no abnormalities on the surface can be observed by visual inspection. "Abnormalities" include, for example, cracks, peeling, and lifting of the coating. Lifting refers to shrinkage or lifting of the optical interference layer. As long as no abnormalities are observed by visual inspection, very slight abnormalities may be observed when observing the sample after the immersion test using a microscope with a magnification of 100 times.

[0055] Furthermore, the alkali resistance can also be evaluated by the change in the optical properties of the cured laminate film before and after the above immersion test. For example, the color difference ΔE in the CIE1976 color space of the cured laminate film before and after the immersion test is preferably 1.5 or less, more preferably 1.0 or less. The CIE1976 color space is specified in JIS Z 8781-4.

[0056] The color difference ΔE is calculated by the following formula. △E=[(△L * ) 2 +(△a * ) 2 +(△b * ) 2 )] 1 / 2 In the formula, △L * is the L before and after the immersion test * The change in △a * is the difference between before and after the immersion test * The change in △b * is the difference between before and after the immersion test. * It represents the amount of change in L * , L * a * b * This is the coordinate that indicates the brightness in the color space. * and b * are L * a * b * These are coordinates that indicate chromaticity in a color space.

[0057] (Stretching rate) Elongation ratio E of laminated film at 160℃ 160is preferably 50% or more. In this case, the laminated film is sufficiently stretched at a molding temperature of 150°C or more and 190°C or less. Therefore, the laminated film can be easily molded into a complex three-dimensional shape without cracking. In particular, damage to the laminated film is easily suppressed in the preforming process. Therefore, a molded product having the functions of a hard coat layer and a light interference layer and a complex three-dimensional shape can be obtained. The laminated film is molded into a three-dimensional shape by, for example, preforming and injection molding depending on the required physical properties, shape, etc.

[0058] Laminated film elongation ratio E 160 is preferably 60% or more, and more preferably 70% or more. 160 may be less than 400%, may be less than 350%, or may be less than 300%. The elongation ratio at 160°C of the molded article obtained by curing the laminated film is less than 15%, and may be 5% or less.

[0059] Stretching ratio E 160 can be measured, for example, as follows. Prepare a tensile tester with a chuck distance of 150 mm and an evaluation sample cut to a length of 200 mm and a width of 10 mm. Stretch the evaluation sample by 10% in the long side direction under conditions of a tensile force of 5.0 kgf and a tensile speed of 300 mm / min in a 160°C atmosphere. Visually check the stretched evaluation sample for the presence or absence of cracks.

[0060] If no cracks are found, a new sample is cut out and stretched in the long side direction by 20%. The presence or absence of cracks is then visually checked in the same manner. This procedure is repeated while increasing the stretching ratio by 10%, and the stretching ratio at which cracks are first found is defined as the stretching ratio E of the laminated film. 160 Let us assume that.

[0061] (Luminous reflectance) Although the surface of the light interference layer is smooth, the laminated film has excellent anti-reflection performance. For example, the luminous reflectance including regular reflection light in the wavelength range of 380 nm to 780 nm measured from the light interference layer side of the laminated film is 0.1% to 4.0%. The molded body obtained by curing the laminated film also has excellent anti-reflection properties. Therefore, the molded body has little reflection due to external light, and has good display characteristics and good visibility. The above-mentioned luminous reflectance of the molded body can be similarly 0.1% to 4.0%.

[0062] The luminous reflectance of the laminate film and the molded article is preferably 0.1% or more and 3.0% or less, and more preferably 0.1% or more and 2.5% or less.

[0063] The luminous reflectance is obtained by measuring all reflected light, including specular reflected light. In other words, the luminous reflectance is measured by the so-called SCI (Specular Component Include) method. This method is not easily affected by the surface condition of the object to be measured, so it is possible to measure the luminous reflectance of an uncured layer.

[0064] Specifically, the luminous reflectance of the laminated film can be measured by the following method. A black paint (e.g., CZ-805 BLACK (manufactured by Nikko Bix Co., Ltd.)) is applied to the surface of the transparent support substrate opposite to the uncured hard coat layer using a bar coater so that the dry film thickness is 3 μm to 6 μm. Then, the substrate is left to dry for 5 hours in a room temperature environment to prepare an evaluation sample M.

[0065] The luminous reflectance of the obtained evaluation sample M from the light interference layer side is measured by the SCI method in the wavelength range of 380 nm to 780 nm using a spectrophotometer (for example, SD7000 manufactured by Nippon Denshoku Industries Co., Ltd.).

[0066] The luminous reflectance of the molded article can be measured as follows. The evaluation sample M created above was irradiated with an integrated light dose of 200 mJ / cm 2or more (for example, cumulative light quantity 2000mJ / cm 2 ) is irradiated with active energy rays to prepare evaluation sample N. The luminous reflectance of the obtained evaluation sample N is measured from the light interference layer side in the same manner as above.

[0067] (hardness) The hardness H measured by the nanoindentation method from the optical interference layer side of the laminated film is considered to be good in terms of preventing damage in the post-processing. BC is preferably 0.05 GPa or more. BC When the pressure is 0.05 GPa or more, defects such as dents and damage during slit formation and cutting, dents due to foreign matter mixed in when multiple laminated films are laminated, squeegee marks or suction marks, etc. are suppressed, and the yield is likely to be improved.

[0068] Hardness H is a good point that adhesion between the uncured hard coat layer and the uncured light interference layer is easily improved. BC The hardness H is preferably 0.5 GPa or less. BC When the hardness is 0.5 GPa or less, when the uncured light interference layer is laminated on the uncured hard coat layer, the two are easily adhered to each other. Furthermore, when the uncured hard coat layer and the uncured light interference layer are laminated by bonding, air is prevented from entering between the layers (air entrapment). BC Specifically, the hardness H is preferably 0.05 GPa or more and 0.5 GPa or less. BC is more preferably 0.15 GPa or more. BC It is more preferable that the pressure is 0.4 GPa or less.

[0069] Accumulated light intensity: 2000mJ / cm 2 The hardness H of the laminate film irradiated with the active energy rays was measured from the optical interference layer side by the nanoindentation method. AC The hardness H is preferably 0.25 GPa or more. AC Hardness H is preferably 0.7 GPa or less. AC Specifically, the hardness H is preferably 0.25 GPa or more and 0.7 GPa or less. AC The hardness H is particularly preferably 0.3 GPa or more. ACmay be 0.6 GPa or less.

[0070] Hardness H of the molded body AC is the hardness H of the laminated film BC In this embodiment, the hardness H AC is 0.25 GPa or more and 0.7 GPa or less, the hardness H BC satisfies 0.1 GPa or more and 0.5 GPa or less.

[0071] Hardness H BC and H AC is calculated based on the value measured by the nanoindentation method from the light interference layer side of the laminated film or molded article. BC and H AC is measured under conditions where the surface condition of the optical interference layer and the hardness of the transparent support substrate are unlikely to have an effect. BC and H AC The hardness H is measured by pressing the indenter from the optical interference layer side into the hard coat layer. BC and H AC It can be said that the hardness reflects the hardness of the uncured or cured hard coat layer. For example, the hardness H BC and H AC is measured within 1000 nm from the surface of the optical interference layer.

[0072] The hardness by the nanoindentation method is determined, for example, by the continuous stiffness measurement method using a nanoindentation device. In the continuous stiffness measurement method, a quasi-static test load (direct current (DC) load) and a minute load (alternating current (AC) load) are applied to the sample. This causes the force acting on the sample to vibrate minutely. The stiffness with respect to depth is calculated from the vibration component of the resulting displacement and the phase difference between the displacement and the load. This allows a continuous profile of hardness with respect to depth to be obtained.

[0073] As a nanoindentation device, an iMicro Nanoindenter manufactured by NANOMECHANICS, INC. can be used. As a continuous stiffness measurement method, for example, the Advanced Dynamic E and H.NMT method can be used. For calculation of load and stiffness, iMicro's dedicated software can be used. A load is applied to the sample by the indenter until a maximum load of 50 mN is reached. As an indenter, for example, a Verkovich type diamond indenter is used. For measurement and stiffness calculation, appropriate values ​​are set for the Poisson's ratio and load of the measurement object (uncured or cured hard coat layer and optical interference layer).

[0074] Hardness H measured by nanoindentation method BC If no indentation remains on the surface of the optical interference layer after the measurement, the measured hardness H BC It can be determined that the hardness H is not accurate. The above phenomenon is considered to occur because the uncured hard coat layer is too soft. In other words, the measured hardness is strongly influenced by the transparent support substrate, not by the uncured hard coat layer. In the above case, the hardness H BC may be considered to be less than 0.05 GPa.

[0075] The transparent supporting substrate and each layer will be described in further detail below. [Transparent support base material] The transparent support substrate is not particularly limited as long as it is transparent. Specifically, being transparent means that the total light transmittance is 80% or more. The total light transmittance of the transparent support substrate is 80% or more, and preferably 90% or more. The total light transmittance can be measured by a method conforming to JIS K 7361-1. As the transparent support substrate, those known in the art can be used without any particular limitation. The transparent support substrate may be colorless or colored.

[0076] The transparent support substrate is appropriately selected depending on the application. Examples of the transparent support substrate include polyester films such as polycarbonate (PC) film, polyethylene terephthalate, and polyethylene naphthalate; cellulose films such as diacetyl cellulose and triacetyl cellulose; acrylic films such as polymethyl methacrylate (PMMA); styrene films such as polystyrene and acrylonitrile-styrene copolymers; olefin films such as polyvinyl chloride, polyethylene, polypropylene, polyolefins having a cyclic or norbornene structure, and ethylene-propylene copolymers; and amide films such as nylon and aromatic polyamide. The transparent support substrate may be a film containing a resin such as polyimide, polysulfone, polyethersulfone, polyetheretherketone, polyphenylene sulfide, polyvinyl alcohol, polyvinylidene chloride, polyvinyl butyral, polyarylate, polyoxymethylene, and epoxy resin, or a film containing a mixture of these polymers.

[0077] The transparent supporting substrate may be a laminate of a plurality of films, for example, a laminate of a film made of an acrylic resin and a film made of a polycarbonate resin.

[0078] The transparent support substrate may be optically anisotropic or isotropic. The magnitude of birefringence of the optically anisotropic transparent support substrate is not particularly limited. The retardation of the anisotropic transparent support substrate may be 1 / 4 (λ / 4) of the wavelength or 1 / 2 (λ / 2) of the wavelength.

[0079] The thickness of the transparent supporting substrate is not particularly limited. The thickness of the transparent supporting substrate is, for example, 50 μm or more and 600 μm or less. In this case, the rigidity of the laminated film after stretching is easily maintained. In addition, the warping of the laminated film and the molded body is easily suppressed. Furthermore, the transparent supporting substrate and the laminated film can be easily wound into a roll, so that roll-to-roll processing can be performed.

[0080] The thickness of the transparent supporting substrate is preferably 100 μm or more, more preferably 200 μm or more, and is preferably 500 μm or less, more preferably 480 μm or less, even more preferably 450 μm or less, and particularly preferably 400 μm or less.

[0081] [Uncured optical interference layer] The uncured light interference layer contains an active energy ray-curable light interference layer-forming composition (hereinafter, sometimes referred to as composition R). Composition R is cured by active energy rays. The hardness and / or elongation ratio of the light interference layer can be controlled by adjusting the integrated light amount of the active energy rays. Composition R is preferably cured by the same type of active energy rays as the hard coat layer-forming composition. The active energy rays are ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays. Composition R is particularly preferably ultraviolet ray-curable.

[0082] The optical interference layer functions as a layer having a low refractive index. The refractive index of the cured optical interference layer is, for example, 1.20 or more and 1.55 or less, may be 1.25 or more and 1.50 or less, or may be 1.30 or more and 1.45 or less. This allows it to exhibit good anti-reflection properties.

[0083] The thickness of the uncured light interference layer is preferably 15 nm or more and 200 nm or less. The thickness of the uncured light interference layer is more preferably 60 nm or more, and particularly preferably 65 nm or more. The thickness of the uncured light interference layer is more preferably 180 nm or less. When the thickness of the uncured light interference layer is in this range, good antireflection properties can be imparted to the molded article.

[0084] The light interference layer is laminated with the uncured hard coat layer in an uncured state. Furthermore, as described above, the laminated film is subjected to various processes in an uncured state. Therefore, in addition to anti-reflection performance, the light interference layer is required to have high hardness, low tack and difficult to be contaminated, damage and appearance changes during processing are suppressed, curling due to differences in heat shrinkage from other layers is suppressed, and the like, similar to the hard coat layer. In particular, the light interference layer is required to have excellent anti-reflection performance, low tack and difficult to be contaminated, and damage during processing (for example, dents such as suction marks and squeegee marks in the decoration process) are suppressed.

[0085] These requirements can be met by controlling the hardness, rigidity, smoothness, tackiness, etc. of the uncured light interference layer. The above physical properties of the uncured light interference layer can be adjusted by the thickness thereof and the composition of the light interference layer-forming composition, etc.

[0086] <<Light interference layer-forming composition>> The optical interference layer-forming composition (composition R) contains, for example, hollow resin particles and a first layer-forming component. The hollow resin particles can lower the refractive index of the optical interference layer while maintaining its strength.

[0087] <Hollow resin particles> Hollow resin particles have spaces (pores) filled with gas inside the resin particles. The number of spaces may be one or more, and may be multiple. The refractive index decreases in inverse proportion to the occupancy rate of the gas. Therefore, hollow resin particles have a lower refractive index than particles without a hollow space.

[0088] The refractive index of the hollow resin particles is preferably 1.1 or more and 1.5 or less, more preferably 1.15 or more, and particularly preferably 1.2 or more, and more preferably 1.45 or less, and particularly preferably 1.4 or less.

[0089] The hollow ratio of the hollow resin particles is not particularly limited and may be appropriately set in consideration of the refractive index and the like. The hollow ratio may be, for example, 10% or more and 90% or less. The hollow ratio is the ratio of the total volume of the internal space to the apparent volume of the hollow resin particles. The hollow ratio is preferably 20% or more. The hollow ratio is preferably 80% or less.

[0090] The resin constituting the hollow resin particles is not particularly limited. Examples of the resin constituting the hollow resin particles include acrylic resin and vinyl resin. From the viewpoint of dispersibility, the resin constituting the hollow resin particles is preferably the same type as the resin component contained in the optical interference layer.

[0091] The hollow resin particles may have an active energy ray curable functional group on the surface. Examples of the active energy ray curable functional group include (meth)acrylic groups. Such hollow resin particles can be obtained by treating the surface of the hollow resin particles with, for example, acrylic acid.

[0092] The film thickness of the light interference layer is designed taking into consideration the average particle diameter of the hollow resin particles. Specifically, the light interference layer is designed not to be excessively thinner than the average particle diameter of the hollow resin particles. This makes it difficult for the hollow resin particles to be exposed from the surface of the light interference layer, and prevents the hollow resin particles from falling off from the light interference layer when the surface of the light interference layer is rubbed. This makes it easier to improve the abrasion resistance.

[0093] In other words, from the viewpoint of abrasion resistance, it is desirable that the average particle diameter of the hollow resin particles is not excessively larger than the film thickness of the light interference layer. On the other hand, from the viewpoint of refractive index, it is desirable that the hollow ratio is large, and it is also desirable that the average particle diameter of the hollow resin particles is large. The average particle diameter of the hollow resin particles used in this embodiment may be 40% or more and 125% or less of the thickness of the uncured light interference layer. Even if the hollow resin particles having such a large particle diameter are included, the light interference layer has high smoothness. The average particle diameter of the hollow resin particles is preferably 45% or more of the thickness of the uncured light interference layer, and more preferably 50% or more. The average particle diameter of the hollow resin particles is preferably 110% or less of the thickness of the uncured light interference layer, and more preferably 95% or less.

[0094] The average particle size of the hollow resin particles is the primary particle size, and is the 50% average particle size (D50) in the volume-based particle size distribution obtained by a laser diffraction / scattering method.

[0095] Specifically, the average particle diameter of the hollow resin particles is preferably 10 nm or more and 150 nm or less. The average particle diameter of the hollow resin particles is more preferably 20 nm or more, and particularly preferably 30 nm or more. The average particle diameter of the hollow resin particles is more preferably 120 nm or less, and particularly preferably 100 nm or less.

[0096] The content of the hollow resin particles is preferably 15 parts by mass or more and 80 parts by mass or less with respect to 100 parts by mass of the solid content of the composition R. This makes it easier for the light interference layer to exhibit excellent antireflection properties while having high smoothness. The content of the hollow resin particles is more preferably 30 parts by mass or more and particularly preferably 40 parts by mass or more with respect to 100 parts by mass of the solid content of the composition R. The content of the hollow resin particles is more preferably 75 parts by mass or less and particularly preferably 70 parts by mass or less with respect to 100 parts by mass of the solid content of the composition R.

[0097] <Other low refractive index particles> The composition R may contain low refractive index particles other than hollow resin particles. However, from the viewpoint of abrasion resistance and alkali resistance, the content is preferably 10 parts by mass or less per 100 parts by mass of the solid content of the composition R. An example of the low refractive index particles is hollow silica particles. The hollow silica particles have, for example, a nanoporous structure.

[0098] <First layer forming component> The first layer-forming component includes a first reactive component having two or more polymerizable functional groups in one molecule. The first reactive component includes at least one selected from the group consisting of a first monomer, a first oligomer, and a first polymer. The weight average molecular weight of the first monomer and the first oligomer is 10,000 or less, and may be 9,000 or less. The weight average molecular weight of the first polymer is more than 10,000, and may be 20,000 or more. The weight average molecular weight of the first polymer may be 100,000 or less.

[0099] The weight average molecular weight (Mw) can be calculated from a chromatogram measured by gel permeation chromatography, based on the molecular weight of standard polystyrene.

[0100] In terms of easiness of improving abrasion resistance, the first reactive component preferably contains at least one of the first monomer and the first oligomer. The total content of the first monomer and the first oligomer is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, relative to 100 parts by mass of the solid content of the composition R. The total content of the first monomer and the first oligomer is preferably 60 parts by mass or less, more preferably 55 parts by mass or less, particularly preferably 50 parts by mass or less, relative to 100 parts by mass of the solid content of the composition R. In one embodiment, the total content of the first monomer and the first oligomer is 5 parts by mass or more and 55 parts by mass or less, relative to 100 parts by mass of the solid content of the composition R.

[0101] The acrylic equivalent of the first monomer and the first oligomer is not particularly limited. In terms of reactivity, the acrylic equivalent of the first monomer and the first oligomer is preferably 100 g / eq. or more, more preferably 110 g / eq. or more, and particularly preferably 115 g / eq. or more. The acrylic equivalent of the first monomer and the first oligomer may be 200 g / eq. or less, 180 g / eq. or less, or 160 g / eq. or less.

[0102] The content of the first polymer is, for example, 20 parts by mass or less per 100 parts by mass of the solid content of the composition R. The content of the first polymer is preferably 1 part by mass or more per 100 parts by mass of the solid content of the composition R. The content of the first polymer is preferably 15 parts by mass or less per 100 parts by mass of the solid content of the composition R.

[0103] From the viewpoint of adhesion to the transparent support substrate and the hard coat layer and transparency, the first reactive component preferably contains a (meth)acrylate compound. Examples of the (meth)acrylate compound include acrylic (meth)acrylate compounds such as acrylic (meth)acrylate monomer, acrylic (meth)acrylate oligomer, and acrylic (meth)acrylate polymer; urethane (meth)acrylate compounds such as urethane (meth)acrylate monomer, urethane (meth)acrylate oligomer, and urethane (meth)acrylate polymer; and silicon (meth)acrylate compounds such as silicon (meth)acrylate monomer, silicon (meth)acrylate oligomer, and silicon (meth)acrylate polymer. These may be used alone or in combination of two or more. "(Meth)acrylate" refers to acrylate and / or methacrylate.

[0104] Examples of (meth)acrylate monomers that are raw materials for (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, acrylic acid, methacrylic acid, isostearyl (meth)acrylate, ethoxylated o-phenylphenol acrylate, methoxypolyethylene glycol acrylate, methoxypolyethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 2-acryloyloxyethyl succinate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, 2-hydroxy-3-methoxypropyl (meth)acrylate, dipentaerythritol hexaacrylate (DPHA), pentaerythritol (tri / tetra)acrylate (PETA), N-methylol (meth)acrylamide, and N-hydroxy(meth)acrylamide.

[0105] The acrylic (meth)acrylate oligomer or polymer may, for example, be a polymerized product of at least one of the above (meth)acrylate monomers.

[0106] The urethane (meth)acrylate monomer or oligomer can also be prepared, for example, by reacting a polycarbonate diol, a (meth)acrylate compound containing a hydroxyl group and an unsaturated double bond group in the molecule, and a polyisocyanate.

[0107] The urethane (meth)acrylate polymer may be, for example, a polymer of at least one of the above-mentioned urethane (meth)acrylate monomers and oligomers.

[0108] Silicone (meth)acrylate compound is a (meth)acrylate compound having a siloxane bond.Although not limited to a specific theory, silicon (meth)acrylate compound can improve the leveling property and reduce tack of uncured hard coat layer.

[0109] The first layer-forming component may include a non-reactive component having less than two polymerizable functional groups in one molecule.

[0110] From the viewpoints of improving abrasion resistance and antifouling properties, decreasing the refractive index, etc., the first reactive component (typically, a (meth)acrylate compound) may contain a fluorine atom. The first layer-forming component may contain a non-reactive component having less than two polymerizable functional groups in one molecule.

[0111] <Inorganic oxide fine particles> The composition R may contain inorganic oxide fine particles. The inorganic oxide fine particles suppress the volumetric shrinkage of the uncured light interference layer and tend to increase the rigidity. Therefore, the appearance change during the manufacturing process of the uncured light interference layer is likely to be suppressed. Furthermore, the appearance change and curling of the cured light interference layer are also suppressed. In addition, the tackiness of the cured light interference layer is reduced and the abrasion resistance is likely to be increased.

[0112] The content of the inorganic oxide fine particles is preferably 20 parts by mass or less, more preferably 18 parts by mass or less, and particularly preferably 15 parts by mass or less, relative to 100 parts by mass of the solid content of the composition R. The content of the inorganic oxide fine particles is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, and particularly preferably 3 parts by mass or more, relative to 100 parts by mass of the solid content of the composition R.

[0113] The inorganic oxide fine particles are not particularly limited. Examples of inorganic oxide fine particles include silica (SiO2) particles (excluding hollow particles), alumina particles, titania particles, tin oxide particles, antimony-doped tin oxide (ATO) particles, and zinc oxide particles. The surface of the inorganic oxide fine particles may be modified with a functional group containing an unsaturated double bond. As the functional group, a (meth)acryloyl group is preferable. Among them, from the viewpoint of cost and paint stability, silica particles and alumina particles are preferable, and silica particles and alumina particles whose surfaces are modified with a functional group are particularly preferable. The form of the inorganic oxide fine particles may be a sol.

[0114] The average particle size of the inorganic oxide fine particles is not particularly limited. From the viewpoint of transparency and the property stability of the composition, the average particle size of the inorganic oxide fine particles is preferably 5 nm or more and 100 nm or less. The average particle size of the inorganic oxide fine particles is a value measured using image processing software from a cross-sectional image obtained by an electron microscope. The average particle size of other granular materials can also be determined by the same method.

[0115] <Photopolymerization initiator> Composition R preferably contains a photopolymerization initiator, which facilitates the polymerization of the active energy ray-curable resin component.

[0116] Examples of the photopolymerization initiator include an alkylphenone-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a titanocene-based photopolymerization initiator, and an oxime ester-based polymerization initiator.

[0117] Examples of alkylphenone-based photopolymerization initiators include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone.

[0118] Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

[0119] An example of the titanocene photopolymerization initiator is bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium.

[0120] Examples of oxime ester polymerization initiators include 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime), oxyphenylacetic acid, 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester, and 2-(2-hydroxyethoxy)ethyl ester. These photopolymerization initiators may be used alone or in combination of two or more.

[0121] Among these, at least one selected from the group consisting of 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 and 2,2-dimethoxy-1,2-diphenylethan-1-one is preferred.

[0122] The content of the photopolymerization initiator is preferably 0.01 parts by mass or more, more preferably 1 part by mass or more, and particularly preferably 3 parts by mass or more, relative to 100 parts by mass of the solid content of the composition R. The content of the photopolymerization initiator is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and particularly preferably 5 parts by mass or less, relative to 100 parts by mass of the solid content of the composition R.

[0123] <Solvent> Composition R may contain a solvent. The solvent is not particularly limited and is appropriately selected in consideration of the components contained in the composition, the type of transparent support substrate, the coating method, and the like.

[0124] Examples of the solvent include aromatic solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone, acetone, methyl isobutyl ketone, and cyclohexanone; ether solvents such as diethyl ether, isopropyl ether, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, anisole, and phenetole; ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, and ethylene glycol diacetate; amide solvents such as dimethylformamide, diethylformamide, and N-methylpyrrolidone; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, and butyl cellosolve; alcohol solvents such as methanol, ethanol, propanol, isopropyl alcohol, butanol, and isobutyl alcohol; and halogen solvents such as dichloromethane and chloroform. These solvents are used alone or in combination of two or more. Among them, ester solvents, ether solvents, alcohol solvents, and ketone solvents are preferred.

[0125] <others> Composition R may contain various additives as necessary, such as antistatic agents, plasticizers, surfactants, antioxidants, UV absorbers, surface conditioners, surface modifiers, leveling agents, and light stabilizers.

[0126] The content of each additive is not particularly limited, and may be appropriately set according to the desired effect. The content of each additive may be, for example, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more, based on 100 parts by mass of the solid content of the composition R. The content of each additive may be 20 parts by mass or less, or 15 parts by mass or less, based on 100 parts by mass of the solid content of the composition R.

[0127] Among them, it is preferable that an ultraviolet absorber and / or a light stabilizer are contained. These additives suppress the photodegradation of the laminate film due to ultraviolet rays. Furthermore, these additives can also suppress the degradation of the laminate film in the process of producing the laminate film and / or the process of producing a molded article using the laminate film. In the above process, the laminate film and its material are heated, so that radicals and active oxygen that deteriorate them are generated. However, the ultraviolet absorber and / or the light stabilizer captures or decomposes these radicals and active oxygen. By suppressing the degradation of the laminate film, etc. in this way, the occurrence of cracks when the laminate film is stretched is further easily suppressed.

[0128] The contents of the ultraviolet absorber and the light stabilizer are each preferably 1 part by mass or more, more preferably 2 parts by mass or more, and particularly preferably 3 parts by mass or more, relative to 100 parts by mass of the solid content of the composition R. The contents of the ultraviolet absorber and the light stabilizer are preferably 10 parts by mass or less, and more preferably 8 parts by mass or less, relative to 100 parts by mass of the solid content of the composition R.

[0129] (UV absorber) Examples of the ultraviolet absorber include at least one selected from the group consisting of benzophenone-based compounds, benzotriazole-based compounds, triazine-based compounds, malonic acid ester-based compounds, cyanoacrylate-based compounds, radical polymerizable compounds, inorganic compounds, and polymers having ultraviolet absorbing properties.

[0130] Examples of benzophenone-based ultraviolet absorbers include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4-methoxybenzophenone, 2, Examples of such benzophenones include 2'-dihydroxy-4,4'-dimethoxybenzophenone (e.g., "UVINUL3049" manufactured by BASF), 2,2',4,4'-tetrahydroxybenzophenone (e.g., "UVINUL3050" manufactured by BASF), 4-dodecyloxy-2-hydroxybenzophenone, 5-benzoyl-2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-stearyloxybenzophenone, and 4,6-dibenzoylresortinol.

[0131] Examples of the benzotriazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-(2-hydroxy-3,5-di-tert-octylphenyl)benzotriazole. 2-[2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenyl]benzotriazole), methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate and polyethylene glycol condensation product (e.g., BASF's "TINUVIN1130"), isooctyl-3-[3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate and polyethylene glycol condensation product (e.g., BASF's "TINUVIN1130"), onate (e.g., "TINUVIN 384" manufactured by BASF), 2-(3-dodecyl-5-methyl-2-hydroxyphenyl)benzotriazole (e.g., "TINUVIN 571" manufactured by BASF), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, triazole, 2-[2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, 2,2-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], and 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (e.g., "TINUVIN 900" manufactured by BASF).

[0132] Other benzotriazole-based ultraviolet absorbents that can be used include BASF's TINUVIN 384-2, TINUVIN 326, TINUVIN 327, TINUVIN 109, TINUVIN 970, TINUVIN 328, TINUVIN 171, TINUVIN 970, TINUVIN PS, TINUVIN P, TINUVIN 99-2, and TINVIN 928 (all trade names).

[0133] Examples of triazine-based ultraviolet absorbers include 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bisbutyloxyphenyl)-1,3,5-triazine (e.g., "TINUVIN460" manufactured by BASF), and 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (e.g., "TINUVIN479" manufactured by BASF).

[0134] Other triazine-based ultraviolet absorbents that can be used include TINUVIN 400, TINUVIN 405, TINUVIN 477, and TINUVIN 1600 (all trade names) manufactured by BASF.

[0135] As the malonic acid ester-based ultraviolet absorber, HOSTAVIN PR25, HOSTAVIN B-CAP, and HOSTAVIN VSU (all trade names) manufactured by Clariant can be used.

[0136] Examples of cyanoacrylate ultraviolet absorbers include ethyl-2-cyano-3,3-diphenylacrylate (e.g., "UVINUL3035" manufactured by BASF), (2-ethylhexyl)-2-cyano-3,3-diphenylacrylate (e.g., "UVINUL3039" manufactured by BASF), and 1,3-bis((2'-cyano-3',3'-diphenylacryloyl)oxy)-2,2-bis-(((2'-cyano-3',3'-diphenylacryloyl)oxy)methyl)propane (e.g., "UVINUL3030" manufactured by BASF).

[0137] Examples of radically polymerizable ultraviolet absorbers include 2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-5-acryloxybenzophenone, 2-hydroxy-5-methacryloxybenzophenone, 2-hydroxy-4-(acryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-diethoxy)benzophenone, 2-hydroxy-4-(acryloxy-triethoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloxyethoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloxyethyl-3-tert-butylphenyl)-2H-benzotriazole (e.g., "RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), 2-(2'-hydroxy-5'-methacryloxypropyl-3-tert-butylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacrylyloxypropyl-3-tert-butylphenyl)-5-chloro-2H-benzotriazole, and 3-methacryloyl-2-hydroxypropyl-3-[3'-(2''-benzotriazolyl)-4-hydroxy-5-tert-butyl]phenylpropionate (e.g., "CGL-104" manufactured by Nippon Ciba-Geigy Ltd.).

[0138] Examples of inorganic ultraviolet absorbents include cerium oxide, zinc oxide, aluminum oxide, zirconium oxide, bismuth oxide, cobalt oxide, copper oxide, tin oxide, and titanium oxide.

[0139] As the polymer having ultraviolet absorbing properties, UV-G101, UV-G301, UV-G137, UV-G12, and UV-G13 (all trade names) manufactured by Nippon Shokubai Co., Ltd. can be used.

[0140] (Light stabilizer) Examples of the light stabilizer include at least one of a hindered amine compound and a polymer having light stability. The polymer having light stability is, for example, an acrylic resin having 2,2,6,6-tetramethyl-4-piperidine as a basic skeleton.

[0141] Examples of the hindered amine light stabilizer include bis(2,2,6,6-tetramethyl-4-piperidyl)succinate, bis(2,2,6,6-tetramethylpiperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-butylmalonate, 1-[2-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]ethyl]-4 -[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propynyloxy]-2,2,6,6-tetramethylpiperidine, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl-1,2,2,6,6-pentamethyl-4-piperidyl-sebacate (e.g., "TINUVIN292" manufactured by BASF), and bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate.

[0142] Other examples of hindered amine light stabilizers that can be used include TINUVIN 123, TINUVIN 144, TINUVIN 152, TINUVIN 249, TINUVIN 292, and TINUVIN 5100 (all trade names) manufactured by BASF.

[0143] The hindered amine light stabilizer includes a radically polymerizable hindered amine compound. Examples of the radically polymerizable hindered amine light stabilizer include 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, 1,2,2,6,6-pentamethyl-4-piperidyl acrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl acrylate, 1,2,2,6,6-pentamethyl-4-iminopiperidyl methacrylate, 2,2,6,6,-tetramethyl-4-iminopiperidyl methacrylate, 4-cyano-2,2,6,6-tetramethyl-4-piperidyl methacrylate, and 4-cyano-1,2,2,6,6-pentamethyl-4-piperidyl methacrylate.

[0144] As the light-stable polymer, U-DOUBLE E-133, U-DOUBLE E-135, U-DOUBLE S-2000, U-DOUBLE S-2834, U-DOUBLE S-2840, U-DOUBLE S-2818, and U-DOUBLE S-2860 (all trade names) manufactured by Nippon Shokubai Co., Ltd. can be used.

[0145] [Uncured hard coat layer] The uncured hard coat layer contains an active energy ray curable hard coat layer forming composition (hereinafter, sometimes referred to as composition HC). The composition HC is cured by active energy rays. The hardness and / or elongation ratio of the hard coat layer can be controlled by adjusting the integrated light amount of the active energy rays. The active energy rays are ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays. The composition HC is preferably an ultraviolet ray curable type. The composition HC is preferably cured by the same type of active energy rays as the composition R.

[0146] The thickness of the uncured hard coat layer is not particularly limited. The thickness of the uncured hard coat layer is, for example, 2 μm or more and 30 μm or less. The uncured hard coat layer is a hard coat layer that has been dried and is not cured (hereinafter, simply referred to as an uncured hard coat layer). When the uncured hard coat layer has such a thickness, warping after curing is easily suppressed. In addition, a hard coat layer having excellent hard coat performance is obtained.

[0147] The thickness of the uncured hard coat layer is more preferably 3 μm or more, and particularly preferably 25 μm or less, and particularly preferably 20 μm or less.

[0148] The hard coat layer is also laminated with the uncured light interference layer in an uncured state. Furthermore, the laminated film is subjected to various processes in an uncured state. Therefore, the uncured hard coat layer is required to have high hardness, low tack and is not easily contaminated, to suppress damage and appearance changes during processing (e.g., foaming and cracks in the preforming process), and to suppress curling due to differences in heat shrinkage from other layers.

[0149] These requirements can be met by controlling the hardness, rigidity, smoothness, tackiness, etc. of the uncured hard coat layer. The above physical properties of the uncured hard coat layer can be adjusted by the thickness thereof and the composition of the hard coat layer-forming composition, etc.

[0150] Hard Coat Layer-Forming Composition The hard coat layer-forming composition (composition HC) contains a second layer-forming component.

[0151] <Second layer forming component> The second layer forming component includes a second reactive component having two or more polymerizable functional groups in one molecule. The second reactive component preferably includes at least one of a second monomer and a second oligomer. This increases the crosslink density of the second layer forming component, making it easier to improve the hardness of the cured hard coat layer. The weight average molecular weight of the second monomer and the second oligomer is 10,000 or less, and may be 9,000 or less.

[0152] The total content of the second oligomer and the second monomer is preferably 25 parts by mass or more and 65 parts by mass or less with respect to 100 parts by mass of the solid content of the composition HC. When the total content of the second oligomer and the second monomer is 25 parts by mass or more with respect to 100 parts by mass of the solid content of the composition HC, the hardness H BC is easily controlled to 0.5 GPa or less. Therefore, the uncured hard coat layer and the uncured light interference layer are easily adhered to each other. Furthermore, when laminating the uncured hard coat layer and the uncured light interference layer, air is easily prevented from entering between the layers (air entrapment). The total content of the second oligomer and the second monomer is more preferably 28 parts by mass or more, particularly preferably 30 parts by mass or more, based on 100 parts by mass of the solid content of the composition HC.

[0153] When the total content of the second oligomer and the second monomer is 65 parts by mass or less per 100 parts by mass of the solid content of the composition HC, the hardness H BC The compressive strength is easily controlled to 0.05 GPa or more. Therefore, defects such as dents and damage during slit formation and cutting, dents due to foreign matter mixed in when multiple laminated films are laminated, squeegee marks or suction marks, etc. are suppressed, and the yield is easily improved. The total content of the second oligomer and the second monomer is more preferably 62 parts by mass or less, particularly preferably 60 parts by mass or less, based on 100 parts by mass of the solid content of the composition HC.

[0154] The solid content of the composition HC is all the components of the composition HC excluding the solvent. The same applies to the solid content of the optical interference layer-forming composition.

[0155] In terms of suppressing the tackiness of the uncured hard coat layer, the second reactive component preferably contains a second polymer having a weight average molecular weight of more than 10,000 together with a second monomer and / or a second oligomer. The weight average molecular weight of the second polymer is more than 10,000 and may be 20,000 or more. The weight average molecular weight of the second polymer may be 100,000 or less.

[0156] The content of the second polymer is preferably 30 parts by mass or more and 70 parts by mass or less relative to 100 parts by mass of the solid content of the composition HC. The content of the second polymer is more preferably 32 parts by mass or more and particularly preferably 35 parts by mass or more relative to 100 parts by mass of the solid content of the composition HC. The content of the second polymer is more preferably 68 parts by mass or less and particularly preferably 65 parts by mass or less relative to 100 parts by mass of the solid content of the composition HC.

[0157] A preferred second reactive component is a (meth)acrylate compound similar to those exemplified as the first reactive component. From the viewpoint of adhesion to the uncured light interference layer and transparency, the second reactive component preferably contains a (meth)acrylate compound.

[0158] <Inorganic oxide fine particles> The composition HC may contain inorganic oxide fine particles. Examples of the inorganic oxide fine particles include those exemplified for the composition R. The content of the inorganic oxide fine particles is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, based on 100 parts by mass of the solid content of the composition HC. The content of the inorganic oxide fine particles is preferably 20 parts by mass or less, more preferably 18 parts by mass or less, and particularly preferably 15 parts by mass or less, based on 100 parts by mass of the solid content of the composition HC.

[0159] <Photopolymerization initiator> The composition HC preferably contains a photopolymerization initiator. This facilitates polymerization of the active energy ray-curable resin component. As the photopolymerization initiator, the same as those exemplified for the composition R can be used.

[0160] Among these, at least one selected from the group consisting of 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 and 2,2-dimethoxy-1,2-diphenylethan-1-one is preferred.

[0161] The content of the photopolymerization initiator is preferably from 0.01 to 10 parts by mass, and more preferably from 1 to 10 parts by mass, relative to 100 parts by mass of the solid content of the composition HC.

[0162] <Solvent> The composition HC may contain a solvent. The solvent is not particularly limited, and is appropriately selected in consideration of the components contained in the composition, the type of transparent support substrate, the coating method, etc. Examples of the solvent include those exemplified for the composition R. Among them, ester-based solvents, ether-based solvents, alcohol-based solvents, and ketone-based solvents are preferred.

[0163] <others> Composition HC may contain various additives as necessary, such as antistatic agents, plasticizers, surfactants, antioxidants, UV absorbers, surface conditioners, surface modifiers, leveling agents, and light stabilizers.

[0164] The content of each additive is not particularly limited, and may be appropriately set according to the desired effect.The content of each additive may be, for example, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more, based on 100 parts by mass of the solid content of the composition HC.The content of each additive may be 20 parts by mass or less, or 15 parts by mass or less, based on 100 parts by mass of the solid content of the composition HC.

[0165] Among them, from the same viewpoint as above, it is preferable to include an ultraviolet absorber and / or a light stabilizer. The content of the ultraviolet absorber and the light stabilizer is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and particularly preferably 3 parts by mass or more, based on 100 parts by mass of the solid content of the composition HC. The content of the ultraviolet absorber and the light stabilizer is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, based on 100 parts by mass of the solid content of the composition HC.

[0166] (UV absorber) Examples of the ultraviolet absorbing agent include at least one selected from the group consisting of benzophenone compounds, benzotriazole compounds, triazine compounds, malonic acid ester compounds, cyanoacrylate compounds, radical polymerizable compounds, inorganic compounds, and ultraviolet absorbing polymers. Specific examples of each compound and polymer include those listed for composition R.

[0167] (Light stabilizer) The light stabilizer may be, for example, at least one of a hindered amine compound and a polymer having light stability. The polymer having light stability may be, for example, an acrylic resin having 2,2,6,6-tetramethyl-4-piperidine as a basic skeleton. Specific examples of the compound and polymer include those mentioned for the composition R.

[0168] The layer-forming components contained in the composition HC and the composition R may be the same or different. In particular, it is preferable that the layer-forming components of both compositions are the same or of the same type. This is because the adhesion between the uncured hard coat layer and the uncured light interference layer is improved, making it difficult for peeling between the layers to occur.

[0169] [Uncured functional layer] The laminated film may further have at least one uncured functional layer between the uncured hard coat layer and the uncured optical interference layer, which reinforces the optical function of the laminated film or imparts a new optical function to the laminated film.

[0170] The functional layer may be another optical interference layer having different optical properties from the optical interference layer described above. The functional layer may be a combination of two or more optical interference layers having different properties from the optical interference layer described above.

[0171] A preferred functional layer is, for example, at least one of a light interference layer having a high refractive index and a light interference layer having a medium refractive index. The refractive index of the high refractive index layer may be greater than 1.55 and less than 2.00. The refractive index of the medium refractive index layer is not particularly limited, and may be between the light interference layer (low refractive index layer) and the high refractive index layer. The refractive index of the medium refractive index layer may be, for example, 1.55 or more and 1.75 or less.

[0172] The thickness of the other optical interference layer is not particularly limited. The thickness of each of the other optical interference layers may be 10 nm or more and 300 nm or less. The thickness of each of the optical interference layers is preferably 15 nm or more, more preferably 20 nm or more, and particularly preferably 40 nm or more. The thickness of each of the optical interference layers is preferably 200 nm or less, more preferably 180 nm or less, and particularly preferably 150 nm or less.

[0173] The functional layer forming composition forming the functional layer may contain the same components as those contained in the above composition HC or composition R. The functional layer forming composition forming the other light interference layer may contain the same components as those contained in composition R. The functional layer forming composition forming the other light interference layer may contain high refractive index particles. The components contained in the multiple functional layers may be the same or different.

[0174] The high refractive index layer and the medium refractive index layer may contain a resin component other than the active energy ray curable type. Examples of the other resin components include thermoplastic resins such as alkyd resins, polyester resins, and acrylic resins; thermosetting resins such as epoxy resins, phenol resins, melamine resins, urethane resins, and silicone resins; and polyisocyanates.

[0175] [Protective film] The laminate film may have a protective film on the surface of the uncured light interference layer opposite to the uncured hard coat layer, which makes it easier to prevent damage to the laminate film when it is wound into a roll or unwound from the roll.

[0176] The protective film protects the optical interference layer and the laminated film, and also functions as a release paper for forming the composition R into a film. In this case, the protective film corresponds to the "other supporting substrate" described later. The protective film may have an adhesive layer on the coating surface.

[0177] Any protective film known in the art may be used without any particular limitation. The protective film may be colorless or colored. The protective film may be transparent.

[0178] The thickness of the protective film is not particularly limited. The thickness of the protective film may be 20 μm or more and 100 μm or less. This makes it easier to improve the protective effect of the uncured light interference layer. The thickness of the protective film is preferably 25 μm or more, more preferably 30 μm or more, even more preferably 33 μm or more, and particularly preferably 35 μm or more. The thickness of the protective film is preferably 85 μm or less, more preferably 80 μm or less, and particularly preferably 65 μm or less. The thickness of the protective film is a value that does not include the thickness of the adhesive layer.

[0179] The protective film is made of, for example, a resin. Examples of the resin film include polyolefin films such as polyethylene films and polypropylene films (including unstretched polypropylene films (CPP films) and biaxially stretched polypropylene films (OPP films)); modified polyolefin films obtained by modifying these; polyester films such as polyethylene terephthalate, polycarbonate, and polylactic acid; polystyrene-based resin films such as polystyrene films, AS resin films, and ABS resin films; nylon films; polyamide films; polyvinyl chloride films; polyvinylidene chloride films; and polymethylpentene films. Among these, at least one selected from polyethylene films, polystyrene films, modified polyolefin films, polymethylpentene films, OPP films, and CPP films is preferred.

[0180] If necessary, the resin film may contain additives such as an antistatic agent, an ultraviolet ray inhibitor, etc. The surface of the resin film may be subjected to a corona treatment or a low-temperature plasma treatment.

[0181] 1 is a cross-sectional view showing a laminated film according to the present embodiment. The laminated film 10 includes a transparent support substrate 11, an uncured hard coat layer 12 disposed on one of the main surfaces of the transparent support substrate 11, and an uncured optical interference layer 13 formed on the uncured hard coat layer 12.

[0182] B. Molded object The molded article according to the present embodiment includes a cured product of the laminated film. The molded article has a transparent support substrate, a cured hard coat layer, and a cured light interference layer. The molded article may further have at least one cured functional layer between the cured hard coat layer and the cured light interference layer. The molded article may or may not further have a protective film. The protective film is used depending on the purpose of use.

[0183] The molded product is, for example, a laminated film molded into a three-dimensional shape, and an integrated light dose of 200 mJ / cm2 The above-mentioned active energy rays are irradiated to completely cure the uncured hard coat layer and the uncured light interference layer, thereby obtaining the above-mentioned optical film.

[0184] The molded article is particularly suitable as a protective material for displays and various sensors arranged around the displays. Examples of the displays include liquid crystal displays, organic EL displays, and plasma displays. The molded article is particularly suitable as a protective material for in-vehicle touch panel displays and their surroundings. The molded article is arranged so that the optical interference layer is on the outer side of the hard coat layer.

[0185] [Decorative layer] The molded article may further include a decorative layer. The decorative layer is a layer that imparts decoration such as a pattern, letters, or metallic luster to the molded article. The decorative layer enhances the design of the molded article.

[0186] The molded article includes, for example, a transparent support substrate, a hard coat layer and an optical interference layer disposed on one main surface of the transparent support substrate, and a decorative layer disposed on the other main surface of the transparent support substrate. The decorative layer may be provided on a part of the other main surface of the transparent support substrate. When the molded article is a protective material for a display, the decorative layer is provided, for example, on a bezel portion surrounding the display.

[0187] The decorative layer may be, for example, at least one of a printed layer and a vapor deposition layer. Each of the printed layer and the vapor deposition layer is one or more layers, and may have a plurality of layers. The thickness of the decorative layer is not particularly limited and is appropriately set according to the design and the like.

[0188] The printed layer may have, for example, a wood grain pattern, a stone pattern, a cloth pattern, a sand pattern, a geometric pattern, letters, or a solid pattern. The printed layer may be formed, for example, from a colored ink containing a binder resin and a colorant. The binder resin is not particularly limited. Examples of the binder resin include polyvinyl resins such as vinyl chloride / vinyl acetate copolymers, polyamide resins, polyester resins, polyacrylic resins, polyurethane resins, polyvinyl acetal resins, polyester urethane resins, cellulose ester resins, alkyd resins, and chlorinated polyolefin resins.

[0189] The colorant is not particularly limited, and may be any known pigment or dye. Examples of yellow pigments include azo pigments such as polyazo, organic pigments such as isoindolinone, or inorganic pigments such as titanium nickel antimony oxide. Examples of red pigments include azo pigments such as polyazo, organic pigments such as quinacridone, or inorganic pigments such as red iron oxide. Examples of blue pigments include organic pigments such as phthalocyanine blue, or inorganic pigments such as cobalt blue. Examples of black pigments include organic pigments such as aniline black. Examples of white pigments include inorganic pigments such as titanium dioxide.

[0190] The deposition layer is formed of at least one metal selected from the group consisting of aluminum, nickel, gold, platinum, chromium, iron, copper, indium, tin, silver, titanium, lead, zinc, etc., or an alloy or compound thereof.

[0191] [Molded resin layer] The molded body may further include a molded resin layer. The molded resin layer supports the hard coat layer and the light interference layer together with the transparent support substrate. The molded body includes, for example, a transparent support substrate, a hard coat layer and a light interference layer disposed on one main surface of the transparent support substrate, and a molded resin layer disposed on the other main surface of the transparent support substrate. The shape of the molded resin layer is not limited. Therefore, the degree of freedom in designing the molded body is increased.

[0192] The molded body may include a transparent supporting substrate, a hard coat layer and an optical interference layer disposed on one main surface of the transparent supporting substrate, a decorative layer disposed on the other main surface of the transparent supporting substrate, and a molded resin layer. In this case, the decorative layer is disposed so as to be sandwiched between the transparent supporting substrate and the molded resin layer.

[0193] The resin (molding resin) forming the molded resin layer is not particularly limited. The molded resin layer includes, for example, a thermosetting resin and / or a thermoplastic resin. Examples of the thermosetting resin include phenolic resin, epoxy resin, melamine resin, urea resin, unsaturated polyester, and thermosetting polyimide. Examples of the thermoplastic resin include so-called engineering plastics. Examples of the engineering plastic include polyamide, polyacetal, polycarbonate, ultra-high molecular weight polyethylene, polysulfone, polyethersulfone, polyphenylene sulfide, and liquid crystal polymer.

[0194] 2 is a cross-sectional view showing a molded body according to the present embodiment. The molded body 20 includes a transparent support substrate 11, a cured hard coat layer 22 disposed on one of its main surfaces, a cured optical interference layer 23 formed on the hard coat layer 22, a decorative layer 24, and a molded resin layer 25. The decorative layer 24 is disposed so as to cover a part of the other main surface of the transparent support substrate 11. The molded resin layer 25 is disposed so as to cover the entire other main surface of the transparent support substrate 11 and the entire decorative layer 24.

[0195] C. Manufacturing method of laminated film The laminated film according to the present embodiment is manufactured by a method including a step of forming an uncured hard coat layer on one side of a transparent support substrate, a step of forming an uncured light interference layer on one side of another support substrate, and a lamination step of laminating the surface of the uncured hard coat layer opposite the transparent support substrate and the surface of the uncured light interference layer opposite the other support substrate to obtain a laminated film. The uncured light interference layer contains hollow resin particles. The arithmetic mean roughness Ra of the surface of the uncured light interference layer of the obtained laminated film is 0.05 μm or less. FIG. 3 is a flowchart showing the method for producing a laminated film according to this embodiment.

[0196] In the process of forming an uncured light interference layer, the outer surface of the light interference layer may have irregularities due to hollow resin particles, while the surface (inner surface) of the light interference layer on the other supporting substrate side is smooth. Then, when the outer surface with irregularities is bonded to the uncured hard coat layer and the other supporting substrate is peeled off, the smooth inner surface of the light interference layer is exposed. This results in a laminated film having a smooth light interference layer. The arithmetic mean roughness Ra of the surface of the uncured light interference layer is measured in a state where the other supporting substrate is peeled off.

[0197] In addition, the lamination method enhances the adhesion between the uncured hard coat layer and the uncured light interference layer while easily suppressing the interphase formation. Therefore, excellent anti-reflection performance is exhibited. The lamination method is a method suitable for producing an after-cure type laminated film.

[0198] (1-1) Step of forming an uncured hard coat layer (S11) The method for forming the uncured hard coat layer is not particularly limited. The uncured hard coat layer is formed, for example, by applying the above-mentioned composition HC onto one surface of a transparent supporting substrate.

[0199] Composition HC can be prepared by a method commonly used by those skilled in the art, for example, by mixing the above-mentioned components using a commonly used mixing device such as a paint shaker or mixer.

[0200] The method of applying the composition HC is not particularly limited, and may be any method commonly used by those skilled in the art. Examples of the application method include dip coating, air knife coating, curtain coating, roller coating, bar coating (e.g., wire bar coating), die coating, inkjet coating, and gravure coating.

[0201] The amount of the composition HC applied is not particularly limited. For example, the composition HC is applied so that the thickness of the uncured hard coat layer after drying is 2 μm or more and 30 μm or less.

[0202] After application, a drying process may be performed. The drying conditions are not particularly limited and are appropriately set so that at least a part of the solvent contained in the composition HC is removed. Examples of the drying method include air drying (natural drying), heat drying, and vacuum drying. Among them, heat drying is preferable. By heating, the uncured hard coat layer can be leveled as well as dried. The drying is performed during the period from when the uncured hard coat layer is formed on the transparent support substrate until the uncured hard coat layer is subjected to a lamination process. For example, the uncured hard coat layer is dried before the transparent support substrate having the uncured hard coat layer is carried into a lamination machine.

[0203] After the uncured hard coat layer is formed, the transparent support substrate may be wound up in a roll shape. This allows roll-to-roll processing up to the lamination step. Furthermore, after a protective film is attached to the surface of the uncured hard coat layer, the transparent support substrate may be wound up. The protective film and the uncured hard coat layer may be attached via an adhesive layer.

[0204] (1-2) Step of forming an uncured optical interference layer (S12) The method of forming the uncured light interference layer is not particularly limited. The uncured light interference layer is formed by, for example, applying the above-mentioned composition R on one side of another supporting substrate (typically the above-mentioned protective film). The preparation and application of the composition R are carried out by a method commonly used by those skilled in the art, similar to the composition HC.

[0205] There is no particular limitation on the amount of application of the composition R. For example, the composition R is applied so that the thickness of the uncured optical interference layer after drying is 15 nm or more and 200 nm or less.

[0206] After coating, a drying step may be performed. Drying conditions are not particularly limited and are appropriately set so that at least a part of the solvent contained in the composition R is removed. As a drying method, the same method as that for drying the hard coat layer may be used. Among them, drying by heating is preferable. By heating, unevenness derived from hollow resin particles may be formed on the outer surface of the uncured light interference layer formed.

[0207] The drying is performed during the period from when the uncured optical interference layer is formed on the other supporting substrate to when the uncured optical interference layer is subjected to a lamination process. For example, the uncured optical interference layer is dried before the other supporting substrate having the uncured optical interference layer is carried into a lamination machine.

[0208] After the uncured optical interference layer is formed, the other supporting substrate may be wound up in a roll shape. This allows roll-to-roll processing up to the lamination step. Furthermore, after a protective film is attached to the surface of the uncured optical interference layer, the other supporting substrate may be wound up. The protective film and the uncured optical interference layer may be attached via an adhesive layer.

[0209] (1-3) Lamination process (S13) The uncured optical interference layer formed on the other supporting substrate and the uncured hard coat layer formed on the transparent supporting substrate are laminated together to obtain a laminated film.

[0210] When the other supporting substrate on which the uncured optical interference layer is formed is wound up, the transparent supporting substrate having the uncured hard coat layer is carried into the laminating machine, and the other supporting substrate that was wound up is carried into the laminating machine while being unwound.

[0211] When the transparent support substrate on which the uncured hard coat layer is formed is wound up, another support substrate having an uncured optical interference layer is carried into the laminating machine, and the wound up transparent support substrate is carried into the laminating machine while being unwound.

[0212] The lamination is preferably performed while applying pressure. The pressure may be, for example, 0.1 N / cm or more and 50 N / cm or less. The pressure is preferably 0.5 N / cm or more. The pressure is preferably 30 N / cm or less.

[0213] The temperature of each layer when bonding is not particularly limited. Since each layer is uncured, they can be bonded at a low temperature. On the other hand, since the occurrence of mixed phases is easily suppressed in the lamination method, each layer may be heated when bonding. The temperature of each layer when bonding may be 0°C or higher and 100°C or lower.

[0214] After the lamination step, the laminated film may be wound into a roll. In this case, it is preferable that the other supporting substrate is not peeled off.

[0215] The obtained laminated film may be heated for leveling. Heating is performed, for example, in an atmosphere of 150° C. to 190° C. for 30 seconds to 60 seconds. Before heating, other supporting substrates may be peeled off. Leveling may be performed by utilizing heat applied in the preforming process.

[0216] A laminate film having an uncured functional layer between an uncured hard coat layer and an uncured light interference layer is produced, for example, by the following process. First, another uncured functional layer is formed on a new support substrate. Then, the surface of the uncured hard coat layer opposite the transparent support substrate is bonded to the surface of the uncured functional layer opposite the new support substrate. After peeling off the new support substrate, the uncured optical interference layer supported by the other support substrate is bonded to the exposed uncured functional layer. If necessary, the process of bonding the uncured functional layer to the uncured hard coat layer or the uncured functional layer laminated thereon is repeated before bonding the optical interference layer.

[0217] This results in a laminated film including, in this order, a transparent supporting substrate, an uncured hard coat layer, at least one uncured functional layer, an optical interference layer, and another supporting substrate. The other supporting substrate may or may not be peeled off.

[0218] 4 is a schematic diagram illustrating the lamination step in the manufacturing method of the laminated film according to the present embodiment. An uncured hard coat layer 12 is formed on one surface of a transparent support substrate 11. This laminate is obtained in the step of forming an uncured hard coat layer. This laminate is transported in a flat state from the left to the right in FIG. 4.

[0219] On the other hand, an uncured light interference layer 13 is laminated on one surface of another supporting substrate 14. This laminate is obtained in a process of forming an uncured light interference layer. This laminate is transported in a flat state from the left to the right in FIG. 4.

[0220] While conveying this laminate, the surface of the uncured hard coat layer 12 opposite the transparent supporting substrate 11 and the surface of the uncured light interference layer 13 opposite the other supporting substrate 14 are bonded together while applying pressure with a pair of rollers 30. This results in a laminate film including the transparent supporting substrate 11, the uncured hard coat layer 12, the light interference layer 13, and the other supporting substrate 14 in this order.

[0221] The dimensions in the illustrated example are merely an example. The thickness and size of each layer and each base material, the position and size of the rollers, etc. may be set as appropriate.

[0222] D. Manufacturing method of molded body The molded article according to this embodiment is produced by a method including a step of molding the above-mentioned laminated film into a desired shape (preferably a three-dimensional shape) and then a curing step of irradiating the laminated film with active energy rays.

[0223] According to one aspect, the molded body according to this embodiment is manufactured by a method including a decoration step of forming a decorative layer on the other main surface of the transparent support substrate of the above-mentioned laminated film, and a curing step of irradiating the laminated film with active energy rays after the decoration step.

[0224] After the decorating step, an injection molding step, or a preforming step and an injection molding step are performed as necessary. In the preforming step, the laminated film is thermoformed into a shape according to a desired three-dimensional shape.

[0225] When the preforming step is performed, the curing step may be performed multiple times. For example, after the preforming step, a semi-curing step may be performed in which active energy rays are irradiated so as to cure a part of the laminated film. In this case, after the injection molding step, a full curing step is performed in which active energy rays are irradiated so as to cure the remaining part of the laminated film. In the full curing step, an integrated light amount of 200 mJ / cm is applied. 2 The above active energy rays are irradiated.

[0226] That is, the molded body is manufactured by a method including, for example, a decorating step (S21), a preforming step (S22), a curing step (S23), and an injection molding step (S24) in this order. Fig. 5 is a flowchart showing a method for manufacturing a molded body according to this embodiment.

[0227] The molded body is also manufactured by a method including, in this order, a decorating step (S21), a preforming step (S22), a semi-curing step (S23-1), an injection molding step (S24), and a main curing step (S23-2). Fig. 6 is a flowchart showing another method for manufacturing a molded body according to this embodiment.

[0228] When the laminate film is wound in a roll, the laminate film may be unwound from the roll and slit or cut into a desired shape and size prior to the decorating step. Each step will be described below.

[0229] (2-1) Decoration process (S21) A decorative layer (typically, a printed layer and a vapor deposition layer) is formed on the other main surface of the transparent supporting substrate of the laminated film.

[0230] The method for forming the printed layer is not particularly limited. Examples of the method for forming the printed layer include offset printing, gravure printing, screen printing, roll coating, and spray coating. The method for forming the vapor deposition layer is also not particularly limited. Examples of the method for forming the vapor deposition layer include vacuum deposition, sputtering, ion plating, and plating.

[0231] (2-2) Preforming process (S22) The laminated film is preformed into a shape that conforms to a desired three-dimensional shape. By forming the laminated film into a shape close to the three-dimensional shape in advance, injection molding (typically, insert mold lamination (IML) molding) becomes possible. In IML molding, the laminated film is inserted into a mold, and a molding resin is injected toward the laminated film. After the preforming process, a trimming process may be performed to remove unnecessary portions of the laminated film.

[0232] The method of preforming is not particularly limited. Preforming is performed, for example, by vacuum molding, pressure molding, or vacuum pressure molding. In preforming, a mold and a laminated film are placed in the same processing chamber. The laminated film is placed so that the transparent support substrate faces the mold. The laminated film is heated to create a vacuum and / or pressure state in the processing chamber. This causes the laminated film to deform along the mold. The laminated film is then cooled and removed from the mold. During preforming, the laminated film may be heated at 90°C or higher and 190°C or lower for 20 seconds to 5 minutes.

[0233] (2-3) Semi-curing process (S23-1) The laminate film is irradiated with active energy rays so that a portion of the laminate film is cured. This results in a semi-cured laminate film. The semi-curing step prevents the laminate film from sticking to the mold in the injection molding step, and adjusts the laminate film to a stretch ratio required for the injection molding step, thereby preventing cracks from occurring in the injection molding step. The integrated light amount of the active energy rays is, for example, 1 mJ / cm. 2 More than 200mJ / cm 2 After the semi-curing step, a trimming step may be carried out to remove unnecessary portions of the laminated film.

[0234] The type of active energy rays is not particularly limited. The active energy rays are appropriately selected depending on the type of resin component contained in the layer-forming composition. The active energy rays are not particularly limited, and may be ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays. Among them, ultraviolet rays having a wavelength of 380 nm or less are preferred. The ultraviolet rays are irradiated using, for example, a high-pressure mercury lamp or an ultra-high-pressure mercury lamp.

[0235] (2-4) Injection molding process (S24) In the injection molding, for example, the optical interference layer is placed opposite a metal mold, and a molding resin is injected toward the transparent supporting substrate, whereby the laminated film is shaped to the shape of the metal mold, and a molding resin layer is formed on the other main surface of the transparent supporting substrate.

[0236] (2-5) Curing process (S23), main curing process (S23-2) The laminated film is irradiated with active energy rays to completely cure the laminated film. This results in a molded product. The cumulative amount of active energy rays used in the process of completely curing the laminated film is 200 mJ / cm. 2 That's all. The cumulative amount of active energy rays is 5000mJ / cm 2 or less than 3000 mJ / cm 2 The active energy rays may be the same as or different from those in the semi-curing step.

[0237] The above-mentioned embodiment is merely an example, and known treatments, processing steps, etc. may be introduced as desired. EXAMPLES

[0238] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are based on mass unless otherwise specified. Hereinafter, the second polymer and the first polymer may be collectively referred to as reactive polymers. Similarly, the second monomer and the first monomer may be collectively referred to as reactive monomers, and the second oligomer and the first oligomer may be collectively referred to as reactive oligomers.

[0239] The components used in the examples and comparative examples are as follows. (Reactive Polymer) Acrylic polymer A: Mw70,000 Acrylic polymer B: Mw 20,000

[0240] Acrylic polymers A and B were prepared as follows. [Preparation of Acrylic Polymer A] A mixture consisting of 30.0 parts of 2,3-epoxypropyl methacrylate, 70 parts of methyl methacrylate, and 1.5 parts of t-butylperoxy-2-ethylhexanoate was prepared. Separately, 40.0 parts of toluene was charged into a 500 ml reaction vessel equipped with a stirring blade, a nitrogen inlet tube, a cooling tube, and a dropping funnel, and the mixture was heated to 110°C. While stirring the reaction vessel, the mixture was dripped at a constant speed over 2 hours under a nitrogen atmosphere. After the dripping was completed, the reaction was carried out for 1 hour under a temperature condition of 110°C. Then, a mixed solution of 1.0 part of t-butylperoxy-2-ethylhexanoate and 25.0 parts of toluene was dripped into the reaction vessel over 1 hour. Next, the reaction vessel was heated to 145°C and reacted for another 2 hours. Next, the reaction vessel was cooled to 110°C or less, and 59.0 parts of toluene were added to obtain precursor A1.

[0241] In another reaction vessel of the same shape as above, 226.5 parts of precursor A1, 15.66 parts of acrylic acid, 0.43 parts of hydroquinone monomethyl ether, and 56 parts of toluene were charged, and the mixture was heated to 90°C while blowing air into the reaction vessel and stirring. Under the temperature condition of 90°C, a mixed solution of 3.0 parts of toluene and 0.81 parts of tetrabutylammonium bromide was further added to the reaction vessel, and the mixture was reacted for 1 hour. Then, the mixture was heated to 105°C, and the reaction was carried out under the temperature condition of 105°C until the acid value of the solid content in the reaction solution became 8 or less. Then, a mixed solution of 0.43 parts of hydroquinone monomethyl ether and 3.0 parts of toluene was added to the reaction solution, and the temperature was set to 75°C. Then, a mixed solution of 10.1 parts of Karenz MOI (manufactured by Showa Denko), 5.0 parts of toluene, and 0.043 parts of dibutyltin dilaurate was added, and the mixture was reacted for 2 hours under the temperature condition of 70°C. Thereafter, the mixture was cooled to 60° C. or less, and a mixed solution of 2.0 parts of methanol and 10.0 parts of toluene was added thereto, thereby obtaining an acrylic polymer A having a weight average molecular weight of 70,000.

[0242] The acid value was measured in accordance with JIS K5601-2-1 by titrating the reaction solution with 0.1 N potassium hydroxide (KOH) solution and calculating according to the following formula: acid value = {(amount of KOH solution dropped [ml]) × (molar concentration of KOH solution [mol / L])} / (mass of solids [g]). The same applies below.

[0243] [Preparation of Acrylic Polymer B] A mixture consisting of 30.0 parts of 2,3-epoxypropyl methacrylate, 70 parts of methyl methacrylate, and 10.0 parts of t-butylperoxy-2-ethylhexanoate was prepared. Separately, 40.0 parts of toluene was charged into a 500 ml reaction vessel equipped with a stirring blade, a nitrogen inlet tube, a cooling tube, and a dropping funnel, and the mixture was heated to 110°C. While stirring the reaction vessel, the mixture was dripped at a constant speed over 2 hours under a nitrogen atmosphere. After the dripping was completed, the reaction was carried out for 1 hour under a temperature condition of 110°C. Then, a mixed solution of 1.0 part of t-butylperoxy-2-ethylhexanoate and 25.0 parts of toluene was dripped into the reaction vessel over 1 hour. Next, the reaction vessel was heated to 145°C and reacted for another 2 hours. Next, the reaction vessel was cooled to 110°C or less, and 59.0 parts of toluene were added to obtain precursor B1.

[0244] In another reaction vessel of the same shape as above, 306.5 parts of precursor B1, 15.66 parts of acrylic acid, 0.43 parts of hydroquinone monomethyl ether, and 56 parts of toluene were charged, and heated to 90°C while blowing air and stirring. Under a temperature condition of 90°C, a mixed solution of 3.0 parts of toluene and 0.81 parts of tetrabutylammonium bromide was further added to this reaction vessel, and reacted for 1 hour. Then, the reaction was heated to 105°C, and the reaction was carried out under a temperature condition of 105°C until the acid value of the solid content in the reaction solution became 8 or less. Then, a mixed solution of 0.43 parts of hydroquinone monomethyl ether and 3.0 parts of toluene was added to the reaction solution, and the temperature was set to 75°C. Then, a mixed solution of 10.1 parts of Karenz MOI (manufactured by Showa Denko), 5.0 parts of toluene, and 0.043 parts of dibutyltin dilaurate was added, and the reaction was carried out for 2 hours under a temperature condition of 70°C. Thereafter, the mixture was cooled to 60° C. or less, and a mixed solution of 2.0 parts of methanol and 10.0 parts of toluene was added thereto, thereby obtaining an acrylic polymer B having a weight average molecular weight of 20,000.

[0245] (Reactive Oligomer) KRM-8452: Daicel Allnex, multifunctional urethane acrylate oligomer, Mw 3,884, acrylic equivalent 120g / eq

[0246] (Reactive Monomer) Aronix M-402: Toagosei Co., Ltd., DPHA

[0247] (Inorganic oxide fine particles) OSCAL 1842: JGC Catalysts and Chemicals Co., Ltd., reactive silica organosol, particle size 10 nm

[0248] (Hollow resin particles) Hollow resin particles A: Hollow acrylic particles, average particle diameter 80 nm, refractive index 1.28 Hollow resin particles B: Hollow acrylic particles, average particle size 80 nm, refractive index 1.28, containing radical polymerizable groups Hollow resin particles C: Hollow acrylic particles, average particle size 80 nm, refractive index 1.31, containing radical polymerizable groups

[0249] (Hollow Silica Particles) Surulia 4320: JGC Catalysts, average particle size 55 nm

[0250] (Highly refractive particles) NANON5 ZR-010: Solar, zirconium oxide, average particle size 20 nm

[0251] (Photopolymerization initiator) Omnirad 127: IGM RESINS, α-hydroxyacetophenone Omnirad 184: IGM RESINS, α-hydroxyalkylphenone

[0252] (Surface conditioner) Optool DAC-HP: Manufactured by Daikin Industries, Ltd. (Surface Modifier) Megafack RS-57: DIC (Light stabilizer) TINUVIN292: BASF Japan

[0253] (Transparent support base material) TB1: Product name: AW-10U, manufactured by Wavelock Advanced Technology Co., Ltd., two-layer film made of PMMA and PC (PMMA / PC), thickness 300 μm

[0254] (Protective film) Torayfan #40-2500, Toray Industries, biaxially oriented polypropylene film (OPP), thickness 40 μm

[0255] [Preparation of Composition LR1] 1.8 parts of acrylic polymer B (reactive polymer), 16.8 parts of Aronix M-402 (reactive monomer), 11.2 parts of Optool DAC-HP (surface conditioner), 12.3 parts of Megafac RS-57 (surface modifier), 3.0 parts of TINUVIN292 (light stabilizer), and 3.4 parts of Omnirad127 (photopolymerization initiator) were mixed. Furthermore, 51.5 parts of hollow resin particles A (hollow resin particles) were blended. This mixture was diluted with propylene glycol monomethyl ether to prepare a milky white composition LR1 with a solid content concentration of 3%. The refractive index of the layer formed by the composition LR1 was 1.20 or more and 1.55 or less.

[0256] [Preparation of compositions LR2-LR7] Milky white compositions LR2-LR7 with a solid content of 3% were prepared in the same manner as composition LR1, except that the formulations were as shown in Table 1A. The refractive indexes of the layers formed from compositions LR2 to LR7 were all 1.20 or more and 1.55 or less.

[0257] [Preparation of Functional Layer-Forming Composition HR1] A milky white functional layer-forming composition HR1 having a solid content of 3% was prepared in the same manner as composition LR1, except that the composition was formulated as shown in Table 1B. The refractive index of the layer formed by composition HR1 was greater than 1.55 and less than or equal to 2.00.

[0258] [Preparation of Composition HC1] As shown in Table 1C, 31.0 parts of acrylic polymer A (reactive polymer), 35.2 parts of KRM-8452 (reactive oligomer), 20.7 parts of ARONIX M-402 (reactive monomer), 3.0 parts of TINUVIN 292 (light stabilizer), 4.0 parts of OSCAL 1842 (inorganic oxide fine particles), and 6.1 parts of Omnirad 184 (photopolymerization initiator) were mixed. This mixture was diluted with methyl isobutyl ketone to prepare a transparent composition HC1 with a solid content concentration of 35%.

[0259] [Example 1] (1) Manufacturing of laminated films (1-1) Formation of an uncured optical interference layer Composition LR1 was applied to TORAYFAN #40-2500 (protective film) by a gravure coater so that the thickness after drying was 120 nm. Then, the composition was dried at 80°C for 1 minute to volatilize the solvent, forming an uncured light interference layer. The protective film on which the uncured light interference layer was formed was wound into a roll. Hereinafter, the light interference layers formed from the compositions LR1 to LR7 may be referred to as "LR layers."

[0260] (1-2) Formation of uncured hard coat layer Composition HC1 was applied to the PMMA surface of transparent supporting substrate TB1 by a gravure coater so that the thickness after drying would be 12 μm. Then, the composition was dried at 80° C. for 1 minute to volatilize the solvent, thereby forming an uncured hard coat layer. Hereinafter, the hard coat layer formed from the composition HC1 may be referred to as an "HC layer."

[0261] (1-3) Lamination of uncured HC layer and LR layer While unrolling the protective film wound in a roll, the surface of the uncured HC layer supported by the transparent support substrate TB1 was laminated with the surface of the uncured LR layer supported by the protective film. This produced a laminated film having the transparent support substrate, the uncured HC layer, the uncured LR layer, and the protective film in this order. Finally, the laminated film was wound in a roll so that the protective film was on the inside.

[0262] (2) Manufacturing of molded bodies (2-1) Formation of decorative layer First, the laminated film was unwound from the roll and cut into the desired shape and size. A decorative (printed) layer was formed by screen printing on the surface of the transparent support substrate of the cut laminated film opposite to the uncured HC layer, and dried at a drying temperature of 80°C for 10 minutes. This decoration process was repeated five times, and then dried at 90°C for 1 hour. A black paint (RIM Ink Gokukoku, manufactured by Jujo Chemical Co., Ltd.) was used to form the printed layer.

[0263] (2-2) Peeling off the protective film Next, the protective film was peeled off from the uncured LR layer at a speed of 5.0 mm / sec. Thereafter, the obtained laminated film was subjected to a heat treatment at 160° C. for 30 seconds.

[0264] (2-3) Preform The laminated film with the printed layer was heated at 190° C. for 30 seconds, and a preform was formed by vacuum and pressure molding using a three-dimensional mold with a maximum depth of 6 mm.

[0265] (2-4) Hardening Accumulated light dose of 2000mJ / cm2 on preformed laminated film 2 The specimen was then irradiated with active energy rays of 1000 .mu.m. Then, trimming was carried out.

[0266] (2-5) Injection molding Finally, injection molding was performed to obtain a molded article having a molded resin layer (polycarbonate) on the printed layer side of the transparent support substrate. In the examples, unless otherwise specified, ultraviolet light was used as the active energy ray.

[0267] [evaluation] The laminated film and the molded article were subjected to the following evaluations, and the results are shown in Table 2. (a) Thickness An evaluation sample of 10 mm x 10 mm was cut out from the laminated film. The cross section of the evaluation sample was precipitated with a microtome (LEICA RM2265). The precipitated cross section was observed with a laser microscope (VK8700, manufactured by KEYENCE) or a transmission electron microscope (JEM2100, manufactured by JEOL Ltd.), and the thicknesses of the HC layer and the LR layer were measured at 10 points. The average values ​​were taken as the thicknesses of the HC layer and the LR layer, respectively.

[0268] (b) Luminous reflectance A black paint (product name: CZ-805 BLACK (manufactured by Nikko Bix Co., Ltd.) was applied to the surface of the transparent support substrate of the laminated film opposite the uncured HC layer using a bar coater so that the dry film thickness was 3 μm to 6 μm. Next, the laminated film coated with the black paint was left to dry in a room temperature environment for 5 hours to prepare an uncured evaluation sample.

[0269] The luminous reflectance of the evaluation sample was measured from the light interference layer side by the SCI method and evaluated. The measurement was performed using SD7000 manufactured by Nippon Denshoku Industries Co., Ltd., and the measurement wavelength range was 380 nm to 780 nm.

[0270] (c) Stretching rate A test piece measuring 200 mm in length and 10 mm in width was cut out from the laminated film. This test piece was set in a tensile tester with a chuck distance of 150 mm, and the evaluation sample was stretched by 10% in the long side direction under conditions of a tensile force of 5.0 kgf and a tensile speed of 300 mm / min in an atmosphere of 160°C. The evaluation sample after stretching was visually checked for the presence or absence of cracks.

[0271] If no cracks were found, a new evaluation sample was cut out and stretched by 20% in the long side direction. The presence or absence of cracks was then visually confirmed in the same manner. This procedure was repeated while increasing the stretch ratio by 10% each time. The stretch ratio at which cracks were first found was taken as the stretch ratio of the laminated film. The above evaluation was carried out three times for evaluation samples cut out from the same laminated film, and the average of the stretch ratios obtained each time was taken as the stretch ratio E of the laminated film. 160 It was decided.

[0272] (d) Arithmetic mean roughness A test piece measuring 200 mm in length and 10 mm in width was cut out from the laminated film. The arithmetic mean roughness of this test piece was determined and evaluated in accordance with the provisions of JIS B0601;2001. The surface roughness was measured using an evaluation type surface roughness measuring instrument (laser microscope, manufactured by Mitutoyo Corporation, SURFTEST SJ-201P) with a cutoff wavelength of 2.5 mm or more and a scanning speed of 0.5 mm / sec.

[0273] (e)Hardness The hardness H was measured from the uncured LR layer side of the laminated film and the LR layer side of the molded product. BC and hardness H AC was measured. The hardness was measured by a continuous stiffness measurement method (method used: Advanced Dynamic E and H.NMT) using an iMicro Nanoindenter manufactured by NANOMECHANICS, INC.

[0274] Specifically, a minute AC load was superimposed on a quasi-static test load and applied to the surface of the evaluation sample. The load was applied until it reached a maximum load of 50 mN. A Berkovich-type diamond indenter (tip curvature radius 20 nm) was used as the indenter. Continuous stiffness with respect to depth was calculated from the vibration component of the generated displacement and the phase difference between the displacement and the load, and a profile of hardness with respect to depth was obtained. The hardness at a depth of 1000 nm from this profile was calculated.

[0275] The load and stiffness were calculated using iMicro's dedicated software. For stiffness calculation, the Poisson's ratio of the coating layer was set to 0.35. The load was controlled so that the strain rate (∂P / ∂t) / P was 0.2.

[0276] (f) Pencil hardness The pencil hardness of the LR layer of the molded product was evaluated. The measurement was carried out in accordance with JIS K5600-5-4 (1999), scratch hardness (pencil method).

[0277] (g) Abrasion resistance The surface of the LR layer of the molded product is 4 cm from the surface of the laminated film. 2 The molded article was rubbed 10,000 times with a cotton cloth attached to the friction element while applying a vertical load of 19.6 N per unit area. After that, the surface of the LR layer of the molded article was visually observed. The evaluation criteria were as follows: Good: No visible scratches even after 10,000 rubs Bad: scratches visible after 10,000 rubs

[0278] (h) Alkali resistance An evaluation sample of 10 cm x 10 cm was cut out from the molded body. The entire evaluation sample was immersed in a 0.001N aqueous sodium hydroxide solution and heat-treated at a temperature of 55°C for 4 hours. It was then cooled to room temperature and washed with water. The appearance of the LR layer of the obtained evaluation sample was visually evaluated, and the color was measured according to JIS Z 8781-4 to calculate the color difference ΔE. The evaluation criteria are as follows: Good: No abnormalities in appearance and color difference △E of 1.5 or less Poor: Appearance abnormality is observed or color difference △E is more than 1.5

[0279] [Comparative Example 1] An uncured HC layer was formed on a transparent supporting substrate TB1 in the same manner as in Example 1. Then, the HC layer was irradiated with an integrated light dose of 2000 mJ / cm 2 2 The HC layer was cured by irradiating it with active energy rays. Composition LR1 was applied to the cured HC layer. Composition LR1 was then dried to form an LR layer with a dry thickness of 120 nm. Finally, an integrated light dose of 2000 mJ / cm 2 A pre-cured laminated film was obtained by irradiating the laminated film with active energy rays of 1000 rpm. A molded article was produced from the laminated film in the same manner as in Example 1, and evaluated. The results are shown in Table 2.

[0280] [Examples 2-5, 7, Comparative Example 2] In the same manner as in Example 1, compositions prepared according to the formulations shown in Tables 1A to 1C were used to prepare laminate films and molded articles having the configurations shown in Table 2. The obtained laminate films and molded articles were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0281] [Example 6] An uncured hard coat layer and an uncured light interference layer were formed in the same manner as in Example 1 (1-1) and (1-2), respectively. Separately, a protective film having an uncured functional layer (HR layer) having the composition shown in Table 1B was obtained in the same manner as in the uncured light interference layer forming step (1-1). The protective film having the uncured HR layer formed thereon was wound into a roll. While unrolling this protective film, the surface of the uncured HR layer supported by the protective film and the surface of the uncured HC layer supported by the transparent support substrate were bonded together.

[0282] Next, the protective film was peeled off to expose the uncured HR layer. The uncured LR layer prepared in (1-1) was unwound and laminated to the HR layer. This produced a laminate film and a molded article having an uncured HC layer, an HR layer, and an LR layer in this order. The obtained laminate film and molded article were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0283] [Table 1A]

[0284] [Table 1B]

[0285] [Table 1C]

[0286] [Table 2]

[0287] As can be seen from Table 2, the laminated film according to this embodiment has high smoothness and excellent abrasion resistance. In addition, although the laminated film has a high elongation ratio (50% or more, specifically 70% or more), the molded article obtained from it has excellent hard coat performance (e.g., high hardness) and excellent antireflection properties. Furthermore, the laminated film according to this embodiment had excellent conformability to a mold with a deep three-dimensional shape in the preforming process.

[0288] On the other hand, the laminated film of Comparative Example 1 has poor smoothness and low abrasion resistance. This is believed to be because the hollow resin particles tend to be present near the outer surface during the drying and curing process of composition LR1. In addition, since the laminated film of Comparative Example 1 is cured, it has a low elongation ratio and is prone to cracking during three-dimensional molding.

[0289] The laminated film of Comparative Example 2 has excellent smoothness because it uses hollow silica particles. However, the hollow silica particles have poor adhesion to the resin component of the light interference layer, so they are easily detached during wear, and the detached hollow silica particles are easily damaged by the resin component of the light interference layer due to their hardness. Therefore, the wear resistance is reduced. Furthermore, the hollow silica particles are easily dissolved in alkali, so the alkali resistance is poor. [Industrial Applicability]

[0290] According to the present invention, a laminate film having excellent abrasion resistance can be provided, and therefore, this laminate film is particularly preferably used for producing a protective material for a display. [Explanation of symbols]

[0291] 10 Laminated film 11 Transparent support base material 12 Uncured hard coat layer 13 Uncured optical interference layer 14 Other supporting substrates 20 Molded body 22 Cured hard coat layer 23 Hardened optical interference layer 24 Decorative layer 25 Molding resin layer 30. Laura

Claims

1. A transparent support substrate; an uncured hard coat layer formed on at least one surface of the transparent support substrate; and an uncured optical interference layer formed on the uncured hard coat layer, the uncured light interference layer contains hollow resin particles, The uncured light interference layer has a surface roughness Ra of 0.05 μm or less.

2. Accumulated light quantity 2000mJ / cm 2 The surface of the light interference layer irradiated with the active energy ray of 19.6 N / 4 cm 2 The laminate film according to claim 1 , wherein no scratches are visible on the optical interference layer after being abraded at 60° C. for 10,000 times.

3. 3. The laminated film according to claim 1, wherein the hollow resin particles have an average particle size of 40% or more and 125% or less of a thickness of the uncured light interference layer.

4. the uncured light interference layer contains an active energy ray-curable light interference layer-forming composition, The laminate film according to any one of claims 1 to 3, wherein the content of the hollow resin particles is 15 parts by mass or more and 80 parts by mass or less with respect to 100 parts by mass of a solid content of the optical interference layer forming composition.

5. the uncured light interference layer contains an active energy ray-curable light interference layer-forming composition, The optical interference layer-forming composition includes a first layer-forming component, the first layer-forming component includes a first reactive component having two or more polymerizable functional groups in one molecule, The laminate film according to any one of claims 1 to 4, wherein the first reactive component includes at least one of a first oligomer having a weight average molecular weight of 10,000 or less and a first monomer having a weight average molecular weight of 10,000 or less.

6. 6. The laminate film according to claim 5, wherein a total content of the first oligomer and the first monomer is 5 parts by mass or more and 55 parts by mass or less with respect to 100 parts by mass of a solid content of the optical interference layer-forming composition.

7. Accumulated light quantity 2000mJ / cm 2 The laminated film according to any one of claims 1 to 6, wherein the laminated film is irradiated with active energy rays, and then immersed in a 0.001N aqueous sodium hydroxide solution and heat-treated at a temperature of 55°C for 4 hours, and no abnormal appearance is visually observed on the surface of the optical interference layer.

8. The laminated film according to any one of claims 1 to 7, wherein the stretch ratio of the laminated film at 160°C is 50% or more.

9. The laminate film according to any one of claims 1 to 8, wherein the luminous reflectance including specular reflection light in a wavelength range of 380 nm to 780 nm measured from the uncured optical interference layer side is 0.1% to 4.0%.

10. The laminate film according to any one of claims 1 to 9, wherein the uncured optical interference layer has a thickness of 15 nm or more and 200 nm or less.

11. The laminate film according to any one of claims 1 to 10, wherein the transparent supporting substrate has a thickness of 50 µm or more and 600 µm or less.

12. The laminate film according to any one of claims 1 to 11, wherein the uncured hard coat layer has a thickness of 2 µm or more and 30 µm or less.

13. The laminate film according to any one of claims 1 to 12, further comprising at least one uncured functional layer between the uncured hard coat layer and the uncured light interference layer.

14. The hardness H measured by a nanoindentation method from the uncured optical interference layer side BC The laminate film according to any one of claims 1 to 13, wherein the modulus of elasticity is 0.05 GPa or more and 0.5 GPa or less.

15. Accumulated light quantity 2000mJ / cm 2 The hardness H measured by a nanoindentation method from the light interference layer side of the laminated film irradiated with active energy rays of AC The laminate film according to any one of claims 1 to 14, wherein the modulus of elasticity is 0.25 GPa or more and 0.7 GPa or less.

16. The uncured hard coat layer contains an active energy ray-curable hard coat layer-forming composition, The hard coat layer-forming composition includes a second layer-forming component, the second layer-forming component includes a second reactive component having two or more polymerizable functional groups in one molecule, The laminate film according to any one of claims 1 to 15, wherein the second reactive component includes at least one of a second oligomer having a weight average molecular weight of 10,000 or less and a second monomer having a weight average molecular weight of 10,000 or less.

17. The laminate film of claim 16 , wherein the second reactive component further comprises a second polymer having a weight average molecular weight of greater than 10,000.

18. The laminate film according to claim 16 or 17, wherein a total content of the second oligomer and the second monomer is 25 parts by mass or more and 65 parts by mass or less with respect to 100 parts by mass of a solid content of the hard coat layer forming composition.

19. A molded article comprising the cured laminate film according to any one of claims 1 to 18.

20. A step of forming an uncured hard coat layer on one surface of a transparent support substrate; forming an uncured optical interference layer on one surface of another supporting substrate; a lamination step of bonding a surface of the uncured hard coat layer opposite to the transparent support substrate and a surface of the uncured light interference layer opposite to the other support substrate to obtain a laminated film, the uncured light interference layer contains hollow resin particles, the uncured light interference layer of the resulting laminate film has an arithmetic mean roughness Ra of 0.05 μm or less.

21. A decorating step of forming a decorative layer on the other main surface of the transparent support substrate of the laminate film according to any one of claims 1 to 18; The method for producing a molded body includes, after the decorating step, a curing step of irradiating the laminate film with active energy rays.

22. The method for producing a molded article according to claim 21 , further comprising, after the decorating step, an injection molding step of opposing the optical interference layer to a mold and injecting a molding resin toward the decorative layer.

23. The mold imparts a three-dimensional shape to the laminate film, The method for producing a molded article according to claim 22, further comprising, after the decorating step and before the injection molding step, a preforming step of molding the laminate film into a shape that conforms to the three-dimensional shape.

Citation Information

Patent Citations

  • Process for producing antireflection base material and antireflection base material

    JP2009037064A

  • Antireflection film

    JP2015004937A

  • Surface protection panel, multilayer member and image display device each using same, and method for producing surface protection panel

    WO2021020222A1

  • Layered film and layered member

    WO2021020301A1

  • Method for manufacturing layered film, and method for manufacturing layered member

    WO2021020302A1